Method for preparing a pharmaceutical composition and pharmaceutical composition
Patent Information
- Application Number
- JP2020153558
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-13
- Filing Date
- 2020-09-14
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-09-14
Smart Images

Figure 0007640065000004 
Figure 0007640065000005 
Figure 0007640065000006
Abstract
Description
[Technical field]
[0001] The present application relates to a method for preparing a pharmaceutical composition, and to the pharmaceutical composition. The present application also provides a method for stabilizing a pharmaceutical compound that is poorly soluble in water. [Background technology]
[0002] At present, water-insoluble drugs account for about 40% of the market for drugs on the market. The water-insolubility of drugs causes a series of problems in the body, such as low bioavailability, excessive drug use and drug waste. It is desirable to improve the dissolution and bioavailability of such drugs. Summary of the Invention
[0003] A method for improving the dissolution and bioavailability of poorly water-soluble pharmaceuticals has been discovered. When nanostructured cellulose is used as a matrix for pharmaceutical compounds, it can stabilize the compounds and prevent the compounds from precipitating, resulting in the compounds remaining in the dispersion. By using a dispersion, gravity-induced aggregation, flocculation, coagulation and / or adhesion of the pharmaceuticals is prevented or significantly reduced. The dissolution rate of the pharmaceutical compounds is increased, thereby enhancing the delivery of the compounds to the target.
[0004] This makes it possible to provide a wide variety of pharmaceutical compositions for different applications, such as oral, topical or injectable compositions.
[0005] The present application provides a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a solvent capable of at least partially solubilizing said pharmaceutical compound; Providing an aqueous dispersion of nanostructured cellulose; and combining said pharmaceutical compound with said aqueous dispersion of nanostructured cellulose in a non-solvent process to provide nano-sized pharmaceutical particles having an average diameter of 50 nm or less; The present invention provides a method for preparing a pharmaceutical composition comprising the steps of:
[0006] The present application also provides a method for stabilizing pharmaceutical compounds that have low water solubility.
[0007] The present application also provides a pharmaceutical composition comprising nano-sized pharmaceutical particles of a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a nanostructured cellulose matrix, said nano-sized pharmaceutical particles having a mean diameter of 50 nm or less, the pharmaceutical composition preferably comprising 92-99.95% (w / w) water.
[0008] The present application also provides a pharmaceutical composition for use as a medicament for stabilizing a pharmaceutical compound, preferably having a solubility in water of 1 mg / ml or less at 25°C.
[0009] The present application also provides a pharmaceutical composition for use as a medicament for enhancing the bioavailability of a pharmaceutical compound, preferably having a solubility in water of 1 mg / ml or less at 25°C.
[0010] The present application also provides the use of nanostructured cellulose for stabilizing pharmaceutical compounds that have low water solubility.
[0011] The present application also provides the use of nanostructured cellulose to enhance the bioavailability of pharmaceutical compounds that have low water solubility.
[0012] The main embodiments are characterized in the independent claims. Various embodiments are disclosed in the dependent claims. The embodiments and examples recited in the claims and in the description can be freely combined with each other, unless expressly stated otherwise.
[0013] Without being bound by any particular theory, the inventors believe that the large specific surface area and network structure of nanostructured cellulose provide more sites for poorly soluble drug compound cores, prevent drug compound particles from overgrowing, and make drug compound nanoparticles more stable in aqueous solution. The interaction between drug compounds can be electrostatic adsorption and hydrogen bonding. The preparation process promotes the nanoization and dispersion of nano-sized drug particles that are initially present as large particles into several small nanoparticles and maintains them in a form that can be considered as a nanocomposite form.
[0014] The nanostructured cellulose used in the embodiments also provides hydroxyl radical scavenging activity, helping to protect pharmaceutical compounds and maintain them in a stable and active form.
[0015] Thus, it is possible to obtain drug formulations that provide better stability, bioavailability and dissolution rates of the drug. New types of drug formulations can be prepared that can utilize new routes of administration, doses and regimes.
[0016] The resulting pharmaceutical compositions can have extremely high water contents, up to 99.95%, which makes it possible to provide a variety of different types of pharmaceutical formulations for poorly water-soluble compounds. [Brief description of the drawings]
[0017] [Figure 1] Figure 1 is a schematic diagram of the formation of CNC / drug nanocomposite via anti-solvent recrystallization process. [Diagram 2] FIG. 2 shows the chemical structure of naringenin. [Diagram 3] FIG. 3 shows the concept of preparation of CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite. [Figure 4] FIG. 4 shows the concept of preparation of CNF / AZI nanocomposite. [Diagram 5]FIG. 5 shows the FTIR spectra of CNC, pristine NG, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite. [Figure 6] Figure 6 shows the XRD patterns of CNC, pristine NG, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite. [Figure 7] Figures 7(a) and 7(b) show TEM images of NG particles by traditional anti-solvent recrystallization process, Figure 7(c) shows TEM images of CNC / NG nanocomposite, and Figure 7(d) shows TEM images of CNC / CTAB / NG nanocomposite. [Figure 8] Figure 8 shows the dissolution rates of pristine NG, NG particles (traditional anti-solvent recrystallization process), CNC / NG nanocomposite, and CNC / CTAB / NG nanocomposite. [Figure 9] Figure 9 shows the OH· scavenging activity of pristine NG, NG particles (traditional anti-solvent recrystallization process), CNC, CNC / NG nanocomposite, and CNC / CTAB / NG nanocomposite. [Figure 10] FIG. 10 shows the chemical structure of azithromycin. [Figure 11] Figure 11(a) shows the dispersion and stability of CNF and CNC in aqueous systems, with 0.1% CNC on the left and 0.1% CNF on the right, and Figure 11(b) shows the dispersion and stability of CNF and CNC in aqueous systems, with 1.5% CNC (liquid) on the left and 1.5% CNF (gel) on the right. [Figure 12] Figure 12(a) shows a TEM image of CNF, bar 20 μm, Figure 12(b) shows a TEM image of CNF, bar 0.5 μm, and Figure 12(c) shows a TEM image of CNC, bar 0.5 μm. [Figure 13] FIG. 13 shows the FTIR spectra of CNC and CNF. [Figure 14] FIG. 14 shows the XRD patterns of CNC and CNF. [Figure 15]FIG. 15 shows the FTIR spectra of CNF, pristine AZI and CNF / AZI nanocomposite. [Figure 16] FIG. 16 shows the XRD patterns of AZI and CNF / AZI nanocomposite. [Figure 17] Figure 17(a) shows a TEM image of pristine AZI. Figure 17(b) shows a TEM image of AZI particles (anti-solvent recrystallization process). Figure 17(c) shows a TEM image of pure CNF. Figure 17(d) shows a TEM image of CNF / AZI nanocomposite. [Figure 18] FIG. 18 shows the OH trapping ratios of CNF and CNC. [Figure 19] FIG. 19 shows the dissolution rates of pristine AZI, AZI particles (traditional anti-solvent recrystallization process), CNF / AZI nanocomposite, and CNC / AZI nanocomposite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In this specification, percentage values are based on weight (w / w) unless otherwise stated. When numerical ranges are provided, the ranges are inclusive of the upper and lower limits. The open term "comprise" also includes as an alternative the closed term "consisting of."
[0019] One of the main challenges associated with poorly soluble drugs is their extremely low bioavailability. Poorly water-soluble drugs often require high doses to reach therapeutic plasma concentrations. It is not always possible to use oil-based carriers. For example, there are compounds that are poorly soluble in oils due to their high melting points, in which case these are less applicable to lipid-based delivery.
[0020] Drug supersaturation often occurs in the intestinal lumen and can develop during the dispersion and digestion of the formulation. This can lead to precipitation of the drug. When a pharmaceutical compound precipitates in crystalline form, it is usually absorbed incompletely.
[0021] The solubility of a formulation can be defined as both quantitative and qualitative. Quantitative solubility is defined as the milligrams of solute particles required to prepare a saturated solution. Qualitative solubility is defined as the situation where two phases mix to form a homogeneous solution.
[0022] With the introduction of new methods such as combinatorial chemistry and high throughput screening, the molecular weight of newly developed active agents increases and their lipophilicity decreases, thus reducing their water solubility.
[0023] There are some instances where an active compound exhibits low solubility, such as when the active compound has 5 or more carbon atoms, when the value of log P is 2 or more, or when the molecular weight of the compound is greater than 500 Daltons. These above instances are called Lipinski's rule, which indicates the active compound as water insoluble or poorly water soluble.
[0024] Compounds with a solubility below 1 mg / ml face significant obstacles, and even compounds below 10 mg / ml often present formulation difficulties related to dissolution. These poorly water-soluble compounds on the market often tend to exhibit suboptimal performance due to low levels of absorption and the effect of food intake when delivered orally.
[0025] Biopharmaceutical drug classification can be based on the recognition of drug dissolution and gastrointestinal permeability as the fundamental parameters controlling the rate and extent of drug absorption.
[0026] The United States Pharmacopeia (USP 23) and BP classify solubility for quantification only, regardless of the solvent used.
[0027] [Table 1]
[0028] Pharmaceutical compounds suitable for the present methods and compositions may be classified as very slightly soluble and / or substantially insoluble, such as requiring at least 1000 parts of solvent per part solute (pharmaceutical compound), for example at least 5000 parts of solvent per part solute, or at least 10000 parts of solvent per part solute. Slightly soluble compounds may also be applied.
[0029] Another classification is the Biopharmaceutic Classification System (BCS), which classifies drugs as BCS-I to BCS-IV. The BCS is a scientific framework for classifying drug substances based on solubility, permeability, and dissolution criteria. According to the BCS, drug substances are classified as follows: Class I: High permeability and solubility Class II: High permeability and low solubility Class III: Low permeability and high solubility · Class IV: Low permeability and low solubility.
[0030] Pharmaceutical compounds suitable for the present methods and compositions may be classified as Class IV compounds, and optionally as Class II compounds, according to the BCS classification. In general, it has been considered an extremely difficult task to improve the parameters of drugs belonging to BCS-IV.
[0031] For purposes of classification, the US regulatory agency, the Food and Drug Administration (FDA), considers a drug highly soluble if the highest active ingredient strength is soluble in less than 250 ml of water over the pH range of 1 to 7.5. A drug substance is considered highly permeable by the FDA if the extent of absorption in humans is determined to be greater than 90% of the administered dose, based on mass balance or compared to an intravenous reference dose.
[0032] It has been found that by using nanostructured cellulose as a matrix, vehicle and / or carrier material, specific nanocomposite structures containing pharmaceutical compounds, preferably nanocomposites containing nanoparticulate pharmaceutical compounds, form in the nanostructured cellulose matrix. These nanocomposites can increase the dissolution rate and bioavailability of pharmaceutical compounds, even when compounds with inherently poor water solubility and / or low bioavailability are used. The dissolution rate can be 50% faster or even 90% faster in 10 minutes compared to the corresponding non-complexed drug particles. It has been shown that the dissolution rate can be at least 50%, at least 70%, at least 80% or at least 85% in 10 minutes, at least 90%, at least 95% or even at least 99% in 120 minutes. The dissolution rate is 50% or more faster or even 90% or more faster compared to the matrix containing the non-complexed drug. In one embodiment, the pharmaceutical compound has a dissolution rate from the nanostructured cellulose matrix of 50% or more in 10 minutes, such as in the range of 50-90% in 10 minutes.
[0033] The present application provides methods and compositions for stabilizing pharmaceutical compounds or enhancing the bioavailability of pharmaceutical compounds. More particularly, the present application provides a method for stabilizing a pharmaceutical compound having low water solubility, preferably below 1 mg / ml, comprising preparing a pharmaceutical composition according to the methods described herein to stabilize the pharmaceutical compound.
[0034] The present application also provides a method for enhancing the bioavailability of a pharmaceutical compound that has low solubility in water, preferably below 1 mg / ml, comprising preparing a pharmaceutical composition by the method described herein.
[0035] The present application also provides a use of nanostructured cellulose for stabilizing a pharmaceutical compound.The present application also provides a use of nanostructured cellulose for enhancing the bioavailability of a pharmaceutical compound.
[0036] The present application provides a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a solvent capable of at least partially solubilizing said pharmaceutical compound; Providing an aqueous dispersion of nanostructured cellulose; and combining said pharmaceutical compound with said aqueous dispersion of nanostructured cellulose in a non-solvent process to provide nano-sized pharmaceutical particles having an average diameter of 50 nm or less; The present invention provides a method for preparing a pharmaceutical composition or a pharmaceutical product, comprising:
[0037] The present application also provides a pharmaceutical composition or pharmaceutical product obtained by said process. A pharmaceutical product is an isolated product and may be provided in a ready-to-use state, such as packaged, incorporated into a carrier or vehicle, and / or otherwise prepared for use. Intermediate products of the process are excluded from the definition.
[0038] The product may be in a form having a very high water content of 92-99.95% (w / w), making the resulting composition or product suitable for various administration forms. The composition may exist as a fluid dispersion, but may also exist as a hydrogel. In one example, a dispersion of nanostructured cellulose comprises a hydrogel.
[0039] For example, the injectable composition may have a water content of 92-99.95% (w / w) and / or a nanostructured cellulose content of 0.05-8% (w / w). The nanostructured cellulose content may range from 1-8% (w / w), such as 1-7% (w / w) or 1-6% (w / w), particularly when it is desired that the composition is in the form of a hydrogel.
[0040] In specific embodiments where nanostructured cellulose is provided primarily as a dispersant, the content of nanostructured cellulose may be in the range of 0.05-0.5% (w / w), such as 0.05-0.4% (w / w) or 0.1-0.5% (w / w), which does not form a gel. In these cases, the water content may be in the range of 99.4-99.95% (w / w), such as 99.5-99.95% (w / w). The content of nanostructured cellulose may also be in the range of, for example, 0.05-1.4% (w / w), 0.1-1.4% (w / w), 0.05-3% (w / w), 0.1-3% (w / w), 0.5-3% (w / w), or 1-5% (w / w). An appropriate concentration may be selected depending on the intended application. The composition may contain nanostructured cellulose as the only polymeric material in the composition, the composition may contain substantially only pharmaceutical compounds, nanostructured cellulose and water, or may consist of pharmaceutical compounds, nanostructured cellulose and water. Optionally, small amounts of additives customary in the art, such as colorants, preservatives or similar agents, which preferably have no effect on the structure of the composition, may be included, preferably in an amount of 0.5% (w / w) or less, such as 0.2% (w / w) or less, or 0.1% (w / w) or less.
[0041] The water content can be calculated or adjusted accordingly, for example by adding up the percentages of the nanofibrillar cellulose and the pharmaceutical ingredient, and possibly any optional additives, with the remainder being water.
[0042] A pharmaceutical compound may have low solubility in water and / or low bioavailability. Low solubility may refer to any of the low solubilities disclosed herein, such as solubility of 1 mg / ml or less, 0.6 mg / ml or less, or 0.3 mg / ml or less at 25°C. A pharmaceutical compound may have a solubility of 0.1 mg / ml or less in water at 25°C, meaning that extremely low solubility causes problems in most applications involving aqueous environments. Solubility may be even lower, such as 0.05 mg / ml or less or 0.02 mg / ml or less at 25°C for very poorly soluble compounds. Solubility may be determined by using any suitable method or standard, such as the USP 25, which is a spinning disk method. In many cases, the solubility of a compound is determined computationally, such as by using ALOGPS software (e.g., ALOGPS 2.1).
[0043] Examples of poorly water-soluble pharmaceutical compounds include naringenin, which has a water solubility of 0.214 mg / ml (ALOGPS), azithromycin (BCS-II, ALOGPS), which has a water solubility of 0.514 mg / ml at 25°C, repaglinide, an example of a zwitterionic drug with a water solubility of 37 mg / l, and atazenavir, which is practically insoluble in water as a free base (<1 mg / l) and has shown low oral bioavailability in preclinical animal models. Additionally, carprofen has a very low water solubility of 0.00379 mg / ml (3.79 μg / ml) at neutral pH, as does itraconazole, which has a solubility of 1 μg / l (0.001 μg / ml). Other examples of drugs with poor water solubility and / or low bioavailability include carbamazepine, gabapentinin, modafinil, piroxicam, caffeine, camptothecin, vinpocetine, fenofibrate, tacrolimus, lopinavir / ritonavir, nabilone, nimodipine, fenofibrate, etravirine, porphyrins, minoxidil, peptides and anthracyclines, cyclosporine A, diazepam, dexamethasone palmitate, etomidate, flurbiprofen, prostaglandin-E1, propofol, perfluorodecalin and perfluorodecalin. Oral products that form emulsions or microemulsions in the gastrointestinal tract, such as perflurotripropylamine, vitamins A, D, E and K, cyclosporine, calcitrol, clofazimine, doxorcalciferol, dronabinol, dutasteride, isotretinoin, ritonavir, paricalcitol, progesterone, saquinavir, sirolimus, tritionoin, tipranavir, valproic acid, and anticancer drugs such as paclitaxel.
[0044] One or more of the above and / or other pharmaceutical compounds may be included in the pharmaceutical composition described herein. The pharmaceutical compound may or may not include one or more antitumor agents, anticancer agents, antibacterial agents such as antibiotics, antiviral agents, anti-inflammatory agents, antiallergic agents, and analgesic (pain relieving) agents such as opioids or nonsteroidal anti-inflammatory drugs, and / or other drugs disclosed herein. In one example, the pharmaceutical compound is not an analgesic compound, especially when the pharmaceutical composition is in an injectable form. The pharmaceutical compound may be a medicine, i.e., a drug compound, but the term may also include other applicable bioactive substances or drugs, such as plant-derived bioactive agents, e.g., flavonoids.
[0045] Nanostructured cellulose, such as nanocrystalline cellulose or nanofibrillar cellulose, can be used to form nanocomposite structures containing pharmaceutical compounds by using the anti-solvent recrystallization process shown diagrammatically in FIG.
[0046] The pharmaceutical compound discussed herein, which may be poorly water-soluble, may first be provided in a powder or particulate form, such as a dry form. The pharmaceutical compound may also be provided in a solution or dispersion, or the dry form may be formed into a solution or dispersion, preferably with a suitable solvent, which may contain water or may be other than water, such as an organic solvent, or into an aqueous solution, a dispersion or emulsion containing an organic solvent. The solvent may allow the pharmaceutical compound to be at least partially solubilized in the solvent. The pharmaceutical compound may be provided to the method in a solvent. Examples of organic solvents include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 1-octanol, propylene glycol, toluene, acetone, 1,4-dioxane, ethyl acetate, isopropyl myristate, acetonitrile, chloroform, n-hexane, cyclohexane, dimethylsulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), dimethylformamide (DFM), and mixtures thereof. The solvent may be, for example, ethanol, such as absolute ethanol. The solvent may be selected depending on the compound used, for example, depending on the solubility of the compound. Ethanol, especially absolute ethanol, can be a suitable solvent for most compounds. A solution of the pharmaceutical compound, typically a drug, in the solvent is obtained.
[0047] The anti-solvent recrystallization process involves adding an anti-solvent to create supersaturation. Without a suitable carrier, for example when the drug in the solvent is combined with water, the drug particles will aggregate, resulting in a poorly soluble form that usually also has low bioavailability. However, in the present case, the process can be controlled and nano-sized drug particles are obtained, which show improved stability and bioavailability in the final product. When the nanostructured cellulose described herein is provided as a carrier, a drug-nanostructured cellulose nanocomposite is formed and maintained. It has been found that the drug does not precipitate and / or aggregate in this structure, but is stabilized and released efficiently, leading to excellent bioavailability. Such nanocomposites can be used as pharmaceutical compositions and dosage forms for various administrations. This process is described in FIG. 3 using naringenin as an exemplary drug compound and in FIG. 4 using azithromycin as an exemplary drug compound. The process in FIG. 3 uses CNC as a carrier, and the process in FIG. 4 uses CNF as a carrier.
[0048] In this method, a pharmaceutical compound in a suitable solvent is added to nanostructured cellulose in an anti-solvent process, such as that described in the examples. A supersaturated concentration of the compound is obtained. The aqueous nanostructured cellulose dispersion acts as an anti-solvent. In this process, the pharmaceutical compound nucleates in a supersaturated concentration and then continues to grow into nanoparticles with an average diameter of 50 nm or less, such as 40 nm or less, 30 nm or less, or 20 nm or less. More specifically, nanoparticles are obtained in a nucleation process. The obtained nanoparticles are not present as aggregates, but rather separate. The pharmaceutical compound is present in the nanoparticles in an amorphous state, rather than in a highly crystalline form. The size and shape of the nanoparticles can be detected microscopically from the final product, such as by using electron microscopy, as shown in Figures 7, 12, and 17.
[0049] The pharmaceutical compound in a solvent can be combined with the aqueous dispersion of nanostructured cellulose by mixing, such as by using a mixer, agitator, disperser, homogenizer or similar equipment that can also be used to process the nanostructured cellulose.
[0050] In one embodiment, the nanostructured cellulose comprises nanofibrillar cellulose, which may have an average fibril diameter of 200 nm or less, such as in the range of 1 to 200 nm.
[0051] In one embodiment, the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 1000-100000 Pa·s, such as in the range of 5000-50000 Pa·s, and a yield stress of 1-50 Pa, such as in the range of 3-15 Pa, as determined by a rotational rheometer at a concentration of 0.5 weight percent (w / w) in an aqueous medium at 22° C.±1° C.
[0052] In one embodiment, the nanostructured cellulose comprises nanocrystalline cellulose. Nanocrystalline cellulose may have an average fibril diameter in the range of 2-40 nm, such as 2-20 nm, and an average fibril length of 100 nm or more, up to several micrometers, such as in the range of 100-400 nm. Typically, 10% or less of the material has a particle size less than 5 μm. Nanocrystalline cellulose may be produced from cellulose by acid hydrolysis, which removes the amorphous regions to obtain the crystalline regions of cellulose. Nanocrystalline cellulose thus consists essentially of crystalline cellulose and lacks the amorphous regions of cellulose. Nanofibrillar cellulose, on the other hand, contains both crystalline portions as straight portions and amorphous portions that provide fibril kinking. Although both nanostructured cellulose materials share common characteristics and properties, due to structural differences, the two materials may exhibit some distinct properties.
[0053] It has been found that poorly soluble pharmaceutical compounds can be stabilized and their bioavailability increased in nanostructured cellulose dispersions, even in dilute dispersions up to 1% (w / w) or up to 1 mg per 100 μl of pharmaceutical compound in the dispersion / composition.
[0054] The content of the pharmaceutical compound may be in the range of 0.05 to 1 mg per 100 μl of the pharmaceutical composition. In one example, the content of the pharmaceutical compound is in the range of 0.1 to 0.7 mg per 100 μl of the pharmaceutical composition, such as in the range of 0.1 to 0.5 mg per 100 μl of the pharmaceutical composition.
[0055] The content of the pharmaceutical compound may be in the range of 0.05-1% (w / w) of the pharmaceutical composition, such as 0.1-1% (w / w). In one example, the content of the pharmaceutical compound is in the range of 0.1-0.7% (w / w), such as in the range of 0.1-0.5% (w / w).
[0056] The pharmaceutical composition may be provided as a pharmaceutical product or formulation, which may exist as a dispersion or as a hydrogel. In one example, the method includes lyophilizing the resulting pharmaceutical composition.
[0057] The process may include filling the resulting pharmaceutical composition into a vial, capsule, or syringe. The pharmaceutical composition may be provided or present in the form of, or as part of, an oral dosage form, a suppository, a dressing, an injectable dosage form, or an implant, for example.
[0058] Oral dosage forms can be provided, for example, by encapsulating or coating the aqueous dispersion of nanostructured cellulose, preferably hydrogel.This may be necessary because nanostructured cellulose dispersion or hydrogel may not be in a form that can be provided or used as is.However, it is possible to provide pharmaceutical compositions in gel or dispersion form, which can be orally applied by using an applicator such as a syringe, a package such as a membrane, a sheet, or a tearable package that can be formed from a flexible structure of plastic, paper, or a laminate thereof.
[0059] Encapsulation refers to a range of dosage forms and techniques used to enclose a pharmaceutical product in a relatively cheap shell known as a capsule that allows it to be taken orally, for example, or used as a suppository. The two main types of capsules include hard-shell capsules and soft-shell capsules. Hard-shell capsules usually contain dry, powdered ingredients or small pellets that can be made, for example, by the process of extrusion or spheronization. These are divided into two halves: a smaller diameter "body" that is filled and then sealed using a larger diameter "cap". Soft-shell capsules are primarily used for oils and active ingredients that are dissolved or suspended in oils. The present composition can be contained in both types of capsules.
[0060] Both types of capsules can be made from an aqueous solution of a gelling agent such as an animal protein, e.g., gelatin, or a plant polysaccharide or its derivative, such as carrageenan and processed forms of starch and cellulose. Other ingredients can be added to the gelling agent solution, including plasticizers such as glycerin or sorbitol to reduce the hardness of the capsule, colorants, preservatives, disintegrants, lubricants, and surface treatments.
[0061] Nanofibrillar cellulose The starting material for forming hydrogels can be nanofibrillar cellulose, also called nanocellulose, which refers to isolated cellulose fibrils or fibril bundles derived from cellulose raw materials. Nanofibrillar cellulose is based on natural polymers that are abundant in nature. Nanofibrillar cellulose has the ability to form viscous hydrogels in water. Nanofibrillar cellulose production techniques can be based on the degradation of fibrous raw materials, such as grinding an aqueous dispersion of pulp fibers to obtain nanofibrillated cellulose. After the grinding or homogenization process, the resulting nanofibrillar cellulose material is a dilute viscoelastic hydrogel.
[0062] The resulting material is usually present in relatively low concentrations homogeneously distributed in water due to the degradation conditions. The starting material can be an aqueous gel with a concentration of 0.2-10% (w / w), for example 0.2-5% (w / w). Nanofibrillar cellulose can be obtained directly from the degradation of fibrous raw materials. An example of a commercially available nanofibrillar cellulose hydrogel is GrowDex® from UPM.
[0063] Due to its nanoscale structure, nanofibrillar cellulose has unique properties that allow functions that cannot be provided by conventional non-nanofibrillar cellulose. It is possible to prepare materials and products that exhibit properties different from conventional products or products using conventional cellulosic materials. However, due to its nanoscale structure, nanofibrillar cellulose is also a challenging material. For example, dehydration or handling of nanofibrillar cellulose can be difficult.
[0064] Nanofibrillar cellulose may be prepared from cellulose raw materials of plant origin or derived from certain bacterial fermentation processes. Nanofibrillar cellulose is preferably made of plant materials. The raw materials may be based on any plant material containing cellulose. In one example, fibrils are obtained from non-parenchymal plant materials. In such cases, fibrils may be obtained from secondary cell walls. One abundant source of such cellulose fibrils is wood fibers. Nanofibrillar cellulose may be produced by homogenizing fibrous raw materials from wood, which may be chemical pulp. Cellulose fibers are decomposed to produce fibrils with an average diameter of only a few nanometers, which may be 200 nm or less in most cases, resulting in a dispersion of fibrils in water. Fibrils derived from secondary cell walls are essentially crystalline, with a crystallinity of at least 55%. Such fibrils may have different properties than fibrils derived from primary cell walls, for example, dehydration of fibrils derived from secondary cell walls may be more difficult. In general, cellulose sources from primary cell walls such as sugar beet, potato tuber, and banana rachis have microfibrils that are easier to release from the fiber matrix than fibrils from wood, requiring less energy to decompose, however these materials are still somewhat heterogeneous and consist of large fibril bundles.
[0065] The non-wood material may be derived from agricultural waste, grass, or other plant material such as straw, leaves, bark, seeds, husks, flowers, vegetables, or fruits from cotton, corn, wheat, oats, rye, barley, rice, flax, hemp, abaca, sisal, jute, ramie, kenaf, bagasse, bamboo, or reed. The cellulose raw material may also be derived from cellulose-producing microorganisms. The microorganisms may be of the genus Acetobacter, Agrobacterium, Rhizobium, Pseudomonas, or Alcaligenes, preferably of the genus Acetobacter, more preferably of the species Acetobacter xylinumor or Acetobacter pasteurianus.
[0066] It has been found that nanofibrillar cellulose obtained from wood cellulose is preferred for the medical or scientific products described herein. Wood cellulose is available in large quantities and the preparation methods developed for wood cellulose allow the production of nanofibrillar materials suitable for the products. Nanofibrillar cellulose obtained by fibrillating plant fibers, especially wood fibers, is structurally different from nanofibrillar cellulose obtained from microorganisms and has different properties. For example, compared to bacterial cellulose, nanofibrillated wood cellulose is a homogenous, more porous and loose material, which is advantageous for medical applications. Bacterial cellulose is usually used as is without fibrillation similar to plant cellulose, so the material is also different in this respect. Bacterial cellulose is a dense material that easily forms small spheres, so the structure of the material is discontinuous, making it undesirable to use such material in medical applications, especially when homogeneity of the material is required.
[0067] The wood may be from softwoods such as spruce, pine, fir, larch, Douglas fir or hemlock, or from hardwoods such as birch, aspen, poplar, alder, eucalyptus, oak, beech or acacia, or from a mixture of softwoods and hardwoods. In one example, the nanofibrillar cellulose is obtained from wood pulp. The nanofibrillar cellulose can be obtained from hardwood pulp. In one example, the hardwood is birch. The nanofibrillar cellulose can be obtained from softwood pulp. In one example, the wood pulp is chemical pulp. Chemical pulp may be desirable for the products disclosed herein. Chemical pulp is a pure material and can be used in a wide variety of applications. For example, chemical pulp lacks pitch and resin acids present in mechanical pulp and is more sterile or easily sterilizable. In addition, chemical pulp is more flexible, providing advantageous properties for example in medical and scientific materials. For example, highly homogeneous nanofibrillar cellulose materials can be prepared without excessive processing or the need for specific equipment or tedious processing steps.
[0068] Nanofibrillar cellulose, including cellulose fibrils and / or fibril bundles, is characterized by a high aspect ratio (length / diameter). The average length of nanofibrillar cellulose (the median length of a particle, such as a fibril or fibril bundle) may exceed 1 μm, and in most cases is not greater than 50 μm. If the elementary fibrils are not completely separated from one another, the intertwined fibrils may have an average total length, for example, in the range of 1-100 μm, 1-50 μm or 1-20 μm. However, if the nanofibrillar material is highly fibrillated, the elementary fibrils may be completely or nearly completely separated, resulting in a shorter average fibril length, such as in the range of 1-10 μm or 1-5 μm. This is especially true for native grade fibrils that have not been shortened or digested, for example chemically, enzymatically or mechanically. However, heavily derivatized nanofibrillar cellulose may have shorter average fibril lengths, such as in the range of 0.3-20 μm, e.g. 0.3-50 μm, such as 0.5-10 μm or 1-10 μm. Particularly shortened fibrils, such as enzymatically or chemically digested fibrils or mechanically treated material, may have average fibril lengths of less than 1 μm, such as 0.1-1 μm, 0.2-0.8 μm or 0.4-0.6 μm. Fibril length and / or diameter may be estimated microscopically, e.g. using CRYO-TEM, SEM or AFM images.
[0069] The average diameter (width) of nanofibrillar cellulose is less than 1 μm, or 500 nm or less, such as in the range of 1-500 nm, but preferably 200 nm or less, such as in the range of 1-200 nm, 2-200 nm, 2-100 nm or 2-50 nm, or even 100 nm or less or 50 nm or less, or even 2-20 for highly fibrillated materials. The diameters disclosed herein may refer to fibrils and / or fibril bundles. The smallest fibrils are on the scale of elementary fibrils, with average diameters typically in the range of 2-12 nm. Elementary nanofibrils may have straight sections of about 100-200 nm in length followed by sharp kinks along the fibrils. These straight sections are composed of highly crystalline cellulose domains, while the bends are formed by amorphous portions.
[0070] The size and size distribution of the fibrils depend on the refining method and efficiency. For highly refined natural nanofibrillar cellulose, the average fibril diameter including the fibril bundles can be in the range of 2-200 nm or 5-100 nm, for example in the range of 10-50 nm. Nanofibrillar cellulose is characterized by a large specific surface area and a strong ability to form hydrogen bonds. In aqueous dispersions, nanofibrillar cellulose typically appears as a light or turbid gel-like material. Depending on the fiber source, nanofibrillar cellulose obtained from plants, especially wood, may also contain small amounts of other plant components, especially wood components such as hemicellulose or lignin. The amount depends on the plant source.
[0071] Generally, cellulose nanomaterials can be classified into categories according to TAPPI W13021, which provides a standard terminology for cellulose nanomaterials. Not all of these materials are nanofibrillar cellulose. The two main categories are "Nano objects" and "Nanostructured materials". Nanostructured materials include "cellulose microcrystals" (also called CMCs) with diameters of 10-12 μm and length:diameter ratios (L / D)<2, and "cellulose microfibrils" with diameters of 10-100 nm and lengths of 0.5-50 μm. Nano objects include "cellulose nanofibers", which can be classified into "cellulose nanocrystals" (CNCs) with diameters of 3-10 nm and L / D>5, and "cellulose nanofibrils" (CNFs or NFCs) with diameters of 5-30 nm and L / D>50.
[0072] Different grades of nanofibrillar cellulose can be classified based on three main properties: (i) size distribution, length and / or diameter, (ii) chemical composition, and (iii) rheological properties. These properties are not necessarily directly dependent on each other. They can be used in parallel to fully describe the grades. Examples of different grades include native (chemically and / or enzymatically unmodified) NFC, oxidized NFC (high viscosity), oxidized NFC (low viscosity), carboxymethylated NFC and cationized NFC. Within these main grades, there are also subgrades, e.g.: very well fibrillated vs. moderately fibrillated, high vs. low substitution, low vs. high viscosity, etc. The fibrillation technique and chemical pre-modification affect the fibril size distribution. Typically, non-ionic grades have a broad average fibril diameter (e.g., in the range of 10-100 nm or 10-50 nm) and chemically modified grades are much thinner (e.g., in the range of 2-20 nm). The distribution is also narrow for modified grades. Certain modifications, particularly TEMPO oxidation, result in shortening of the fibrils.
[0073] Depending on the raw material source, e.g. hardwood pulp vs. softwood pulp, different polysaccharide compositions are present in the final nanofibrillar cellulose product. Generally, non-ionic grades are prepared from bleached birch pulp resulting in a high xylene content (25 wt%). Modified grades are prepared from hardwood or softwood pulp. In these modified grades, the hemicelluloses are also modified together with the cellulose domains. Presumably, the modification is not homogeneous, i.e., some parts are more modified than others. Thus, detailed chemical analysis is usually not possible, since the modified product is a complex mixture of different polysaccharide structures.
[0074] In an aqueous environment, dispersions of cellulose nanofibrils form viscoelastic hydrogel networks. Gels are already formed at relatively low concentrations, e.g., 0.05-0.2% (w / w), by dispersed and hydrated entangled fibrils. The viscoelasticity of NFC hydrogels can be characterized, e.g., by dynamic oscillatory rheological measurements.
[0075] Nanofibrillar cellulose hydrogels exhibit distinctive rheological properties. For example, they are shear-thinning or pseudoplastic materials, which can be considered as a special case of thixotropic behavior, meaning that their viscosity depends on the speed or force with which the material is deformed. When measuring the viscosity with a rotational rheometer, shear-thinning behavior is seen as a decrease in viscosity with increasing shear rate. Hydrogels exhibit plastic behavior, meaning that a certain shear stress (force) is required before the material begins to flow easily. This critical shear stress is often called the yield stress. The yield stress can be determined from steady-state flow curves measured with a stress-controlled rheometer. When the viscosity is plotted as a function of the applied shear stress, a dramatic decrease in viscosity is seen after the critical shear stress is exceeded. Zero shear viscosity and yield stress are the most important rheological parameters that describe the suspending power of the material. These two parameters provide a very clear separation of the different grades, thus allowing the classification of the grades.
[0076] The size of the fibrils or fibril bundles depends, for example, on the raw material, the decomposition method, and the number of decomposition runs. The mechanical decomposition of the cellulose raw material can be carried out in any suitable equipment, such as a refiner, grinder, disperser, homogenizer, colloid, friction grinder, pin mill, rotor-rotor disperser, ultrasonicator, fluidizer such as microfluidizer, macrofluidizer, or fluidizer-type homogenizer. The decomposition process is carried out under conditions in which there is sufficient water present to prevent the formation of bonds between the fibers. The skilled person can adjust the conditions for preparing nanofibrillar cellulose with the desired rheological properties and degree of fibrillation without undue experimentation, for example, by selecting the appropriate decomposition equipment, the appropriate starting material, the appropriate chemical, physical and / or enzymatic treatment, the number of passes and / or energy used in the process, and the concentration and chemical content of the resulting product.
[0077] In one example, the disintegration is carried out by using a disperser having at least one rotor, blade or similar moving mechanical member, such as a rotor-rotor disperser having at least two rotors. In the disperser, the dispersed fibrous material is repeatedly impacted by the blades or ribs of the rotors striking from opposite directions as the blades rotate in opposite directions at a peripheral speed determined by the rotation speed and the radius (distance to the axis of rotation). As the fibrous material is carried radially outward, it strikes the broad surfaces, i.e., ribs, of successive blades coming from opposite directions at a high peripheral speed; in other words, the fibrous material is subjected to multiple successive impacts from opposite directions. Also, shear forces are generated at the edges of the broad surfaces, i.e., ribs, of the blades that form a blade gap with the opposite edge of the next rotor blade, which contributes to the disintegration of the fibers and the detachment of the fibrils. The impact frequency is determined by the rotation speed of the rotors, the number of rotors, the number of blades of each rotor, and the flow rate of the dispersion through the device.
[0078] In rotor-rotor dispersers, fibrous material is introduced radially outwardly through counter-rotating rotors, relative to the rotor axes, such that the material is repeatedly subjected to shear and impact forces by the effect of the different counter-rotating rotors, thereby simultaneously fibrillating. An example of a rotor-rotor disperser is the Atrex device.
[0079] Another example of a device suitable for decomposition is a pin mill, such as a multi-peripheral pin mill. One example of such a device comprises a housing and a first rotor with an impact surface therein; a second rotor concentric with the first rotor, with an impact surface and arranged to rotate in the opposite direction to the first rotor; or a stator concentric with the first rotor and with an impact surface. The device comprises a feed orifice in the housing, opening towards the centre of the rotor or the rotor and the stator, and a discharge orifice in the housing wall, opening towards the periphery of the outermost rotor or stator.
[0080] In one example, the disintegration is carried out by using a homogenizer, where the fibrous material is subjected to homogenization by the effect of pressure. The homogenization of the fibrous material dispersion into nanofibrillar cellulose is caused by a forced through-flow of the dispersion, which breaks the material into fibrils. The fibrous material dispersion is passed at a given pressure through a narrow through-flow gap, where an increase in the linear velocity of the dispersion causes shear and impact forces on the dispersion, removing the fibrils from the fibrous material. The fibrous pieces are broken down into fibrils in the fibrillation process.
[0081] As used herein, the term "fibrillation" generally refers to mechanically breaking down fibrous material by work applied to the particles, whereby cellulose fibrils are detached from the fibers or fibrous pieces. The work may be based on various effects such as crushing, crushing or shearing, or a combination of these, or another corresponding action that reduces particle size. The expressions "breakdown" or "breakdown process" may be used interchangeably with "fibrillation".
[0082] The fibrous material dispersion subjected to fibrillation is a mixture of fibrous material and water, also referred to herein as "pulp". A fibrous material dispersion may generally refer to whole fibers, parts (pieces) separated from the fibers, fibril bundles, or fibrils mixed with water, and typically the aqueous fibrous material dispersion is a mixture of these elements, where the ratio between the components depends on the degree of processing or processing stages, e.g., the number of processing runs or "passes" of the same batch of fibrous material.
[0083] One way to characterize nanofibrillar cellulose is to use the viscosity of an aqueous solution containing said nanofibrillar cellulose. The viscosity can be, for example, the Brookfield viscosity or the zero shear viscosity. The specific viscosity described herein distinguishes nanofibrillar cellulose from non-nanofibrillar cellulose.
[0084] In one example, the apparent viscosity of nanofibrillar cellulose is measured with a Brookfield Viscometer (Brookfield Viscometer) or another corresponding device. Suitably, a vane spindle (number 73) is used. There are several commercially available Brookfield Viscometers available for measuring the apparent viscosity, all based on the same principle. Suitably, an RVDV spring (Brookfield RVDV-III) is used with the device. A sample of nanofibrillar cellulose is diluted to a concentration of 0.8% by weight in water and mixed for 10 minutes. The diluted sample mass is added to a 250 ml beaker, the temperature is adjusted to 20°C ± 1°C, heated and mixed if necessary. A low rotation speed of 10 rpm is used. In general, Brookfield viscosity can be measured at 20°C ± 1°C, a concentration of 0.8% (w / w) and 10 rpm.
[0085] For example, the nanofibrillar cellulose provided as starting material in the present method may be characterized by the viscosity it provides in an aqueous solution. The viscosity describes, for example, the degree of fibrillation of the nanofibrillar cellulose. In one example, the nanofibrillar cellulose, when dispersed in water, provides a Brookfield viscosity of at least 2000 mPa·s, such as at least 3000 mPa·s, measured at 20°C±1°C at a concentration of 0.8% (w / w) and 10 rpm. In one example, the nanofibrillar cellulose, when dispersed in water, provides a Brookfield viscosity of at least 10000 mPa·s, measured at 20°C±1°C at a concentration of 0.8% (w / w) and 10 rpm. In one example, the nanofibrillar cellulose, when dispersed in water, provides a Brookfield viscosity of at least 15000 mPa·s, measured at 20°C±1°C at a concentration of 0.8% (w / w) and 10 rpm. Examples of Brookfield viscosity ranges for the nanofibrillar cellulose when dispersed in water include 2000-20000 mPa·s, 3000-20000 mPa·s, 10000-20000 mPa·s, 15000-20000 mPa·s, 2000-25000 mPa·s, 3000-25000 mPa·s, 10000-25000 mPa·s, 15000-25000 mPa·s, 2000-30000 mPa·s, 3000-30000 mPa·s, 10000-30000 mPa·s, and 15000-30000 mPa·s, measured at a concentration of 0.8% (w / w) and 10 rpm at 20°C ± 1°C.
[0086] Nanofibrillar cellulose may also be characterised by its average diameter (or width), or by its average diameter together with a viscosity such as Brookfield viscosity or zero shear viscosity. In one example, nanofibrillar cellulose suitable for use in the products described herein has an average fibril diameter in the range of 1-200 nm or 1-100 nm. In one example, the nanofibrillar cellulose has an average fibril diameter in the range of 1-50 nm, such as 2-20 nm or 5-30 nm. In one example, the nanofibrillar cellulose has an average fibril diameter in the range of 2-15 nm, such as in the case of TEMPO oxidised nanofibrillar cellulose.
[0087] The fibril diameter can be determined by several techniques, including microscopy. The fibril thickness and width distribution can be measured by image analysis of field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), including cryogenic transmission electron microscopy (cryo-TEM), or atomic force microscopy (AFM) images. In general, AFM and TEM are best suited for nanofibrillar cellulose grades with narrow fibril size distribution.
[0088] The rheometer viscosity of nanofibrillar cellulose dispersions can be measured according to an example at 22 °C using a stress-controlled rotational rheometer (AR-G2, TA Instruments, UK) with narrow gap vane geometry (diameter 28 mm, length 42 mm) in a cylindrical sample cup with a diameter of 30 mm. After loading the sample into the rheometer, the sample is allowed to rest for 5 min before starting the measurement. The steady-state viscosity is measured at gradually increasing shear stress (proportional to the torque applied) and shear rate (proportional to the angular velocity). The reported viscosity at constant shear stress (=shear stress / shear rate) is recorded after a constant shear rate is reached or after a maximum of 2 min. 1000 s -1 The measurements are stopped once the shear rate exceeds 0. This method can be used to determine the zero shear viscosity.
[0089] In another example, rheological measurements of hydrogel samples were performed using a stress-controlled rotational rheometer (AR-G2, TA Instruments, UK) with a 20 mm plate geometry. Samples were loaded undiluted into the rheometer, 1 mm gap, and then the samples were allowed to rest for 5 min before measurements were started. Stress sweep viscosity was measured at 25 °C, at a frequency of 10 rad / s, strain of 2%, and gradually increasing shear stress in the range of 0,001 to 100 Pa. Storage modulus, loss modulus and yield stress / break strength can be determined.
[0090] It was found that there is a minimum viscosity level required for the hydrogel to retain its shape after injection, which can be characterized by a storage modulus of 350 Pa or more and a yield stress / break strength of 25 Pa or more, determined by a stress-controlled rotational rheometer at 25°C, a frequency of 10 rad / s, a strain of 2%, and gradually increasing shear stress in the range of 0.001 to 100 Pa. A person skilled in the art can select the appropriate preparation method and parameters to obtain such characteristics, even when using different types of starting materials such as chemically modified or chemically unmodified cellulose.
[0091] The nanofibrillar cellulose should have a sufficient degree of fibrillation to obtain the desired properties and effects. In one embodiment, the nanofibrillar cellulose has an average diameter of fibrils in the range of 1-200 nm, and / or the nanofibrillar cellulose or pharmaceutical composition, when dispersed in water, has a storage modulus of 350 Pa or more, such as in the range of 350-5000 Pa, or preferably in the range of 350-1000 Pa, and a yield stress of 25 Pa or more, such as in the range of 25-300 Pa, preferably in the range of 25-75 Pa, as determined by a stress-controlled rotational rheometer at 25° C., a frequency of 10 rad / s, a strain of 2%, and gradually increasing shear stress in the range of 0.001-100 Pa.
[0092] In one example, the nanofibrillar cellulose, for example provided as a starting material in the present method, when dispersed in water, has a zero shear viscosity (a "plateau" of constant viscosity at small shear stress) of 1000-100000 Pa·s, such as in the range of 5000-50000 Pa·s, and a yield stress (shear stress at which shear thinning begins) of 1-50 Pa, such as in the range of 3-15 Pa, as determined by a rotational rheometer at a concentration of 0.5% by weight (w / w) in aqueous medium at 22° C.±1° C. Such nanofibrillar cellulose may also have an average fibril diameter of 200 nm or less, such as in the range of 1-200 nm.
[0093] Turbidity is the cloudiness or haze of a fluid caused by individual particles (fully suspended or dissolved solids) that are generally not visible to the naked eye. There are several practical ways to measure turbidity, the most direct being the measurement of the attenuation (i.e., reduction in intensity) of light as it passes through a sample column of water. The Jackson Candle method, used instead (units: Jackson Turbidity Units or JTU), is essentially an inverse measure of the length of a column of water required to completely obscure a candle flame seen through the column of water.
[0094] Turbidity can be quantitatively measured using an optical turbidity meter. There are several commercial turbidity meters available to quantitatively measure turbidity. In this case, a nephelometric based method is used. The unit of turbidity from a calibrated nephelometer is called Nephelometric Turbidity Units (NTU). The measuring device (turbidimeter) is calibrated and controlled with a standard calibration sample and the turbidity of a subsequently diluted NFC sample is measured.
[0095] In one turbidity measurement method, a nanofibrillar cellulose sample is diluted in water to a concentration below the gel point of the nanofibrillar cellulose and the turbidity of the diluted sample is measured. The concentration at which the turbidity of the nanofibrillar cellulose sample is measured is 0.1%. A HACH P2100 turbidimeter equipped with a 50 ml measuring vessel is used for the turbidity measurement. The dry matter of the nanofibrillar cellulose sample is measured and 0.5 g of sample calculated as dry matter is filled into the measuring vessel, which is filled with tap water to 500 g and mixed vigorously by shaking for about 30 seconds. The aqueous mixture is divided into five measuring vessels without delay and inserted into the turbidimeter. Three measurements are carried out for each vessel. The mean value and standard deviation are calculated from the obtained results and the final result is given in NTU.
[0096] One way to characterize nanofibrillated cellulose is to define both viscosity and turbidity. Low turbidity refers to small size fibrils, such as small diameter, since small fibrils scatter very little light. Generally, as the degree of fibrillation increases, the viscosity increases and the turbidity decreases at the same time. However, this occurs up to a certain point. If the fibrillation continues further, the fibrils eventually begin to break and can no longer form a robust network. Thus, from this point onwards, both turbidity and viscosity begin to decrease.
[0097] In one example, the turbidity of anionic nanofibrillar cellulose is less than 90 NTU, e.g., 3-90 NTU, such as 5-60 NTU, e.g., 8-40 NTU, measured by nephelometry at a concentration of 0.1% (w / w) in an aqueous medium. In one example, the turbidity of native nanofibrils may be greater than 200 NTU, e.g., 10-220 NTU, e.g., 20-200 NTU, e.g., 50-200 NTU, measured by nephelometry at a concentration of 0.1% (w / w) in an aqueous medium at 20° C.±1° C. These ranges can be combined with viscosity ranges of nanofibrillar cellulose, such as zero shear viscosity, storage modulus and / or yield stress, to characterize the nanofibrillar cellulose.
[0098] The nanofibrillar cellulose may be or may include unmodified nanofibrillar cellulose. The drainage of unmodified nanofibrillar cellulose is significantly faster than, for example, anionic grades. Unmodified nanofibrillar cellulose generally has a Brookfield viscosity in the range of 2000-10000 mPa·s, measured at 20°C±1°C, at a concentration of 0.8% (w / w) and 10 rpm. It is preferred that the nanofibrillar cellulose has a suitable carboxylic acid content, determined by conductometric titration, in the range of 0.6-1.4 mmol COOH / g, for example in the range of 0.7-1.2 mmol COOH / g, or in the range of 0.7-1.0 mmol COOH / g or 0.8-1.2 mmol COOH / g.
[0099] The degraded fibrous cellulose raw material may be a modified fibrous raw material, which means a raw material whose fibers have been affected by a treatment so that the cellulose nanofibrils can be more easily detached from the fibers. The modification is usually carried out on a fibrous cellulose raw material that is present as a suspension in a liquid, i.e., a pulp.
[0100] The fiber modification treatment can be chemical, enzymatic or physical. In chemical modification, the chemical structure of the cellulose molecule is changed by chemical reaction ("derivatization" of cellulose) so that the length of the cellulose molecule is preferably not affected, but functional groups are added to the β-D-glucopyranose units of the polymer. The chemical modification of cellulose is carried out with a certain degree of conversion that depends on the dosage of the reactants and the reaction conditions, and is not complete in principle, so that the cellulose remains in solid form as fibrils and does not dissolve in water. In physical modification, anionic, cationic or non-ionic substances or any combination of these are physically adsorbed on the cellulose surface.
[0101] The cellulose in the fibers may be particularly ionically charged after modification. The ionic charge of the cellulose weakens the internal bonds of the fiber and promotes its later degradation into nanofibrillar cellulose. The ionic charge may be achieved by chemical or physical modification of the cellulose. The fibers may have a higher anionic or cationic charge after modification compared to the starting material. The most commonly used chemical modification methods to generate anionic charges are oxidation, sulfonation and carboxymethylation, which oxidize hydroxyl groups to aldehyde and carboxyl groups. Chemical modification may be desirable to introduce groups such as carboxyl groups that can participate in the formation of covalent bonds between nanofibrillar cellulose and bioactive molecules. Similarly, cationic charges may be generated chemically by cationization by attaching cationic groups such as quaternary ammonium groups to cellulose.
[0102] Nanofibrillar cellulose may include chemically modified nanofibrillar cellulose, such as anionically modified nanofibrillar cellulose or cationically modified nanofibrillar cellulose. In one example, the nanofibrillar cellulose is anionically modified nanofibrillar cellulose. In one example, the anionically modified nanofibrillar cellulose is oxidized nanofibrillar cellulose. In one example, the anionically modified nanofibrillar cellulose is sulfonated nanofibrillar cellulose. In one example, the anionically modified nanofibrillar cellulose is carboxymethylated nanofibrillar cellulose. Materials resulting from anionic modification of cellulose may be referred to as anionic cellulose, which refers to materials in which the amount or proportion of anionic groups, such as carboxyl groups, is increased by modification, when compared to unmodified materials. It is also possible to introduce other anionic groups, such as phosphate or sulfate groups, into the cellulose instead of or in addition to carboxyl groups. The content of these groups may be within the same ranges as disclosed herein for carboxylic acids.
[0103] The cellulose may be oxidized. In the oxidation of cellulose, the primary hydroxyl groups of cellulose may be catalytically oxidized by heterocyclic nitroxyl compounds, such as 2,2,6,6-tetramethylpiperidinyl-1-oxy free radical, commonly referred to as "TEMPO", through N-oxyl mediated catalytic oxidation. The primary hydroxyl groups (C6-hydroxyl groups) of cellulosic β-D-glucopyranose units are selectively oxidized to carboxyl groups. Some aldehyde groups are also formed from the primary hydroxyl groups. Regarding the observation that a low degree of oxidation does not allow efficient fibrillation and that a high degree of oxidation leads to decomposition of the cellulose after mechanical destruction treatment, the cellulose can be oxidized to a level having a carboxylic acid content in the oxidized cellulose in the range of 0.5-2.0 mmol COOH / g pulp, 0.6-1.4 mmol COOH / g pulp, or 0.8-1.2 mmol COOH / g pulp, preferably 1.0-1.2 mmol COOH / g pulp, as determined by conductometric titration. When the fibers of oxidized cellulose thus obtained are decomposed in water, they give a stable transparent dispersion of individual cellulose fibrils, which may have a width of, for example, 3-5 nm. Using oxidized pulp as the starting medium, it is possible to obtain nanofibrillar cellulose with a Brookfield viscosity measured at a concentration of 0.8% (w / w) of at least 10000 mPa·s, for example in the range of 10000-30000 mPa·s.
[0104] Whenever the catalyst "TEMPO" is mentioned in this disclosure, it is self-evident that all measurements and procedures involving "TEMPO" apply equally well to any derivative of TEMPO or any heterocyclic nitroxyl radical capable of selectively catalyzing the oxidation of the hydroxyl group at the C6 carbon in cellulose.
[0105] The nanofibrillar cellulose modification disclosed herein may also be applied to other fibrillar cellulose grades described herein. For example, highly beaten cellulose or microfibrillar cellulose may be similarly modified chemically or enzymatically. However, there may be differences in the final degree of fibrillation of the material, for example.
[0106] In one example, such chemically modified nanofibrillar cellulose, when dispersed in water, provides a Brookfield viscosity of at least 10,000 mPa·s at a concentration of 0.8% (w / w) and 10 rpm, measured at 20° C.±1° C. In one example, such chemically modified nanofibrillar cellulose, when dispersed in water, provides a Brookfield viscosity of at least 15,000 mPa·s at a concentration of 0.8% (w / w) and 10 rpm, measured at 20° C.±1° C. In one example, such chemically modified nanofibrillar cellulose, when dispersed in water, provides a Brookfield viscosity of at least 18,000 mPa·s at a concentration of 0.8% (w / w) and 10 rpm, measured at 20° C.±1° C. Examples of anionic nanofibrillar celluloses used have, depending on the degree of fibrillation, Brookfield viscosities of 13000 to 15000 mPa·s, or 18000 to 20000 mPa·s, or even up to 25000 mPa·s.
[0107] In one example, the nanofibrillar cellulose is TEMPO oxidized nanofibrillar cellulose, which provides a high viscosity at low concentration, for example a Brookfield viscosity of at least 20000 mPa·s, or even at least 25000 mPa·s, measured at 20° C.±1° C. at a concentration of 0.8% (w / w) and 10 rpm. In one example, the Brookfield viscosity of the TEMPO oxidized nanofibrillar cellulose is in the range of 20000-30000 mPa·s, such as 25000-30000 mPa·s, measured at 20° C.±1° C. at a concentration of 0.8% (w / w) and 10 rpm.
[0108] In one example, the nanofibrillar cellulose comprises chemically unmodified nanofibrillar cellulose, hi one example, such chemically unmodified nanofibrillar cellulose when dispersed in water provides a Brookfield viscosity of at least 2000 mPa s or at least 3000 mPa s, measured at 20° C.±1° C. at a concentration of 0.8% (w / w) and 10 rpm.
[0109] Auxiliary agents can be included in the nanofibrillar cellulose dispersion to enhance the manufacturing process or to improve or adjust the properties of the product. Such auxiliary agents may be soluble in the liquid phase of the dispersion, they may form an emulsion, or they may be solid. The auxiliary agents may be added to the raw materials already during the production of the nanofibrillar cellulose dispersion, or they may be added to the formed nanofibrillar cellulose dispersion or gel. The auxiliary agents may be added to the final product, for example, by impregnation, spraying, immersion, soaking, or similar methods. The auxiliary agents are usually not covalently bound to the nanofibrillar cellulose and may therefore be releasable from the nanocellulose matrix. Controlled and / or sustained release of such agents can be obtained using NFC as a matrix. Examples of auxiliary agents include therapeutic (pharmaceutical) agents and other agents that affect the properties of the product or the properties of the active agent, such as buffers, surfactants, plasticizers, emulsifiers, etc. In one example, the dispersion contains one or more salts that can be added to enhance the properties of the final product or to facilitate the removal of water from the product in the manufacturing process. Examples of salts include chloride salts such as sodium chloride, calcium chloride and potassium chloride. Salts may be included in an amount ranging from 0.01 to 1.0% (w / w) of the dry matter in the dispersion. The final product may be immersed or soaked in a solution of sodium chloride, such as an aqueous solution of about 0.9% sodium chloride. The desired salt content in the final product may range from about 0.5 to 1%, such as about 0.9% of the volume of the wet product. Salts, buffers and similar agents may be provided to obtain physiological conditions.
[0110] Multivalent cations may be included to obtain non-covalent crosslinking of the nanofibrillar cellulose. One example provides a nanofibrillar cellulose product comprising nanofibrillar cellulose, particularly anionically modified nanofibrillar cellulose, and multivalent cations, such as multivalent metal cations selected from calcium, barium, magnesium, zinc, aluminum, gold, platinum and titanium cations, where the nanofibrillar cellulose is crosslinked by the multivalent cations. In particular barium and calcium may be useful for biomedical applications, and in particular barium may be used for labeling and detection of injected hydrogels. The amount of multivalent cations may range from 0.1 to 3% (w / w), for example 0.1 to 2% (w / w), calculated from the dry content of the hydrogel.
[0111] One example provides a method for preparing such a hydrogel, comprising providing pulp, degrading the pulp until nanofibrillar cellulose is obtained, and forming the nanofibrillar cellulose into a hydrogel.
[0112] The nanofibrillar cellulose can be fibrillated to a desired degree of fibrillation, adjusted to a desired water content, or modified to form a gel with desired properties as described herein. In one example, the nanofibrillar cellulose in the hydrogel is anionically modified nanofibrillar cellulose.
[0113] Hydrogels used as medical or scientific hydrogels need to be homogenous. Thus, the method of preparing a hydrogel may comprise homogenizing a hydrogel comprising nanofibrillar cellulose, preferably with a homogenizing device such as the device described herein. This preferably non-fibrillating homogenization step allows to remove discontinuous areas from the gel. A homogenous gel is obtained with better properties for application. The hydrogel may further be sterilized, for example by using heat and / or radiation and / or by adding a germicidal agent such as an antimicrobial agent.
[0114] Use of the composition The compositions comprising pharmaceutical compounds in nanostructured cellulose hydrogels disclosed herein may be used in a variety of ways, including delivering, injecting, implanting and / or otherwise administering the compositions to a subject, such as a human or animal subject. The subject may be a patient, particularly a patient in need of therapy involving the pharmaceutical compound contained in the composition. It may be necessary to recognize or detect the subject in need of treatment. There may be a specific target in the subject to which the pharmaceutical agent is targeted, e.g., injected. The method includes providing a composition comprising pharmaceutical compounds in nanofibrillar cellulose hydrogels in a suitable form, such as an injectable or implantable form. Oral dosage forms may also be provided, e.g., encapsulated in a biodegradable capsule, such as a soft capsule. The treatment, which may be a therapy, may include sustained release administration of one or more pharmaceutical compounds, such as sustained or controlled release administration. Similarly, the pharmaceutical formulation administered may be a sustained release composition or dosage form, such as a sustained or controlled release composition or dosage form. The treatment may include any suitable therapeutic treatment, such as a chronic treatment, or treatment with one or more other suitable pharmaceutical compounds. A pharmaceutical composition may generally be presented for use as a medicament for treating a subject by administration to the subject by a suitable route and / or suitable means of administration.
[0115] One example provides a pharmaceutical composition for use as a medicament for stabilizing a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C., e.g., during storage and / or when administered to a subject.
[0116] One example provides a pharmaceutical composition for use as a medicament for enhancing the bioavailability of a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C., for example when administered to a subject.
[0117] One example is a method of treating a subject in need of treatment, comprising: Preferably, identifying a subject in need of therapy or treatment; Providing a composition comprising a pharmaceutical compound in a nanostructured cellulose hydrogel as disclosed herein; and Delivering or administering the composition to a subject The present invention provides a method comprising: EXAMPLES
[0118] In this study, nanocellulose (nanocrystalline cellulose CNC and nanofibrillar cellulose NFC) dispersions were used as carriers for naringenin (NG) and azithromycin (Azi) to enhance the dissolution rate and antioxidant activity. Based on the formation of CNF / Azi nanocomposites, the dissolution of Azi was significantly enhanced in contrast to pristine Azi in aqueous solution. CNC / NG nanocomposites and CNC / CTAB / NG nanocomposites were successfully prepared based on CNC carrier and anti-solvent recrystallization process.
[0119] Pure CNC also has excellent hydroxyl radical (OH·) scavenging ability due to the large amount of reducing ends of cellulose. It was also confirmed that NFC hydrogels can act as a matrix for water-insoluble or limited water-soluble drug powders (carprofen or meloxicam) to prevent aggregation and coagulation. Nanocellulose dispersions or hydrogels can improve the bioavailability of hydrophobic drugs in aqueous systems.
[0120] Part I: Cellulose nanocrystals (CNCs) as nanocarriers for naringenin to enhance dissolution and bioavailability
[0121] 1. Background Naringenin (NG, 4,5,7-trihydroxyflavanone, Figure 2) is a natural dihydroflavonoid compound. NG is extracted from many kinds of natural products, such as grapefruit, tomato, grapes and citrus fruits. Many studies have revealed that NG has many pharmacological activities, including free radical scavenging in vivo, antitumor, antibacterial, antiviral, anti-inflammatory, antiallergic and antithrombotic activities. However, the medicinal applications of NG are extremely limited due to its poor water solubility and poor lipid solubility.
[0122] In this study, CNC was used as a carrier for NG to enhance the dissolution rate and antioxidant activity. NG was first nanoized through anti-solvent recrystallization and then loaded onto CNC to form CNC / NG nanocomposites. Furthermore, during the preparation of CNC / CTAB / NG nanocomposites, CNCs were coated with cetyltrimethylammonium bromide (CTAB) to increase the hydrophobicity. The obtained CNC / NG nanocomposites and CNC / CTAB / NG nanocomposites were characterized by Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), and X-ray diffraction (XRD) analysis. The dissolution rate and in vitro antioxidant activity (OH· free radical scavenging) were also investigated.
[0123] 2. Research purpose 2.1 Preparation and characterization of CNC / NG nanocomposites and CNC / CTAB / NG nanocomposites; 2.2 Evaluation of the dissolution and antioxidant activity of NG in aqueous systems in CNC / NG nanocomposites and CNC / CTAB / NG nanocomposites.
[0124] 3. Materials and Methods 3.1 Experimental materials and equipment Cellulose nanocrystals (CNCs) were obtained as 98% lyophilized powder from Cellulose Lab Inc. (Fredericton, Canada). Naringenin (NG) was obtained as 98% purity from Aifa Biotechnology Co., Ltd (Chengdu, China).
[0125] The main experimental equipment included an ultrasonic cell disrupter D&DN JY99-IIDN manufactured by Xinzhi Biotechnology Co., Ltd. (Zhejiang, China), a UV-vis spectrophotometer TU-1810PC manufactured by Beijing Puhua General Instrument Co., Ltd. (Beijing, China), a Fourier transform infrared spectrometer Nicolet iS5 manufactured by Thermo Fisher Company (Waltham, USA), a transmission electron microscope JEM-2010 manufactured by Electronics Corporation (Tokyo, Japan), an X-ray diffractometer Bruker D8 Advance manufactured by Bruker Company (Karlsruhe, Germany), and a freeze dryer ALPHA1-2LDPLUS manufactured by Marin Christ Co., Ltd. (Osterode, Germany).
[0126] 3.3 Experimental Method 3.3.1 Preparation of CNC / NG nanocomposites The original NG powder was dissolved in absolute ethanol under ultrasonic dispersion at room temperature to form a solution with a concentration of 25 μg / ml. Then, various volumes of NG ethanol solution were added dropwise to the well-dispersed CNC aqueous solution (60 ml and 0.2 wt.%) with magnetic stirring in an ice-water bath, which was maintained for 10 min. Finally, the obtained CNC / NG nanocomposite suspension was freeze-dried for future use.
[0127] For comparison, NG particles were prepared without CNCs by adding various volumes of NG ethanolic solution (25 μg / ml) dropwise into deionized water (60 ml) under the same conditions (traditional anti-solvent recrystallization process).
[0128] 3.3.2 Preparation of CNC / CTAB / NG nanocomposite A CTAB solution with a concentration of 1 mmol / l was prepared by dissolving a certain amount of CTAB powder in deionized water. 10 ml of the CTAB solution was added dropwise to 100 ml of CNC aqueous solution (0.2 wt.%) with magnetic stirring at room temperature. The resulting CNC / CTAB mixture was heated to 60°C and kept on a shaking table for 30 min, then cooled to room temperature. The resulting reaction product formed a CTAB-modified CNC precipitate, which was for later use.
[0129] A certain amount of NG ethanol solution (25 μg / ml) was added dropwise to the CTAB-modified CNC aqueous suspension (60 ml and 0.2 wt.%) under vigorous stirring in an ice-water bath, which was maintained for 10 min. The obtained CNC / CTAB / NG nanocomposite suspension was freeze-dried for further use.
[0130] 3.3.3 Fourier transform infrared spectroscopy (FTIR) analysis The samples of CNC, pristine NG powder, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite were analyzed and recorded on a Nicolet iS5 FTIR spectrometer (Thermo Fisher, Waltham, USA) at 400 cm -1 ~4000cm -1 Scans were collected over a range of
[0131] 3.3.4 Transmission electron microscope (TEM) observation Samples of CNC, pristine NG powder, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite were diluted to 0.01 wt.% with deionized water, and one drop of the diluted dispersion was transferred onto a carbon-coated copper grid. The grid was then air-dried overnight at room temperature. TEM observations were performed using a JEM 2010 (S)TEM instrument (Japan) operating at an accelerating voltage of 200 keV.
[0132] 3.3.5 X-ray diffraction (XRD) analysis Samples of CNC, pristine NG powder, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite were obtained on a Bruker D8 Advance powder X-ray diffractometer (Germany) operated at an accelerating voltage of 40 kV, and the diffraction intensity of CuKα radiation was measured over a 2θ scan range of 3°–50° at 0.02° / s per step.
[0133] 3.3.6 In vitro dissolution rate of NG (1) Standard NG curve The original NG powder was dissolved in absolute ethanol to form a series of concentrations of NG solutions (2.4 mg / ml, 3.6 mg / ml, 4.8 mg / ml, 6.0 mg / ml, 7.2 mg / ml and 8.4 mg / ml). Ultraviolet (UV) absorption measurements at a wavelength of 290 nm were then performed to determine the concentrations of the NG solutions and obtain a standard NG curve.
[0134] (2) In vitro dissolution rate The dissolution rate was determined according to the method of the 2015 Chinese Pharmacopoeia (XC II). First, 2 mg samples of NG were placed in 100 ml of deionized water and stirred at 100 rpm and 37°C. Then, at pre-scheduled times (1 min, 5 min, 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, 120 min), 5 ml of each sample was taken out and filtered through a 0.22 μm membrane for UV absorption measurement at a wavelength of 290 nm to determine the NG concentration; meanwhile, 5 ml of deionized water was immediately added to the dissolution medium to maintain a constant volume. The dissolution rate of NG was calculated using Equation 1: Dissolution rate (%)=(C n ×V2+C1×V1+C2×V1+…+C n-1 ×V1)×100% / m(1) (In the formula, C1, C2, C n-1 , C n is the NG concentration at the pre-scheduled time, mg / ml; m is the total NG input, mg; V1 is the fixed sampling volume, ml; V2 is the total volume of dissolution medium, ml).
[0135] 3.3.7 In vitro antioxidant activity The in vitro antioxidant activity of the samples was evaluated by measuring the OH· scavenging activity according to the salicylic acid hydroxylation method. In this method, the Fenton reaction was used to generate OH·, which was then scavenged by salicylic acid. The system consisted of 1.8 mM ferrisulphate (2 ml), 1.8 mM salicylic acid (1.5 ml), and 1 ml of sample solution. Finally, 0.1 ml of H2O2 (0.03 wt.%) was added to the mixed solution to start the reaction, and the mixture was incubated at 37 °C for 30 min. After incubation, the UV absorption was measured at a wavelength of 510 nm. The OH· scavenging rate was calculated using Equation 2: OH Capture rate (%)=(A0-A i )×100% / A0(2) (where A0 is the UV absorbance of the control representing the total amount of OH· produced, and Ai is the UV absorbance of the sample).
[0136] 4. Results and Discussion 4.1 Concept of preparation of CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite The flow chart for preparing CNC / NG nanocomposites and CNC / CTAB / NG nanocomposites is shown in Figure 3. In the traditional anti-solvent recrystallization process (Figure 3, a), NG ethanol solution was added dropwise into deionized water under various conditions. With the increase of NG dosage in the anti-solvent, NG nuclei formed at supersaturated concentrations and then continued to grow into NG nanoparticles. Due to their hydrophobic nature, the NG nanoparticles aggregated to form NG aggregates that were difficult to disperse in aqueous solutions.
[0137] As a carrier, CNCs, due to their large surface area and abundant hydrogen bonds, provided more sites for NG nucleation, resulting in the formation of smaller and more uniform NG nanoparticles (Figure 3, b). Furthermore, the excellent hydrophilicity of CNCs allowed the CNC / NG system to be extremely stable, reducing the aggregation and flocculation of the resulting NG nanoparticles. The particle growth of hydrophobic griseofulvin can be inhibited / reduced by using polymers and surfactants such as poly(vinylpyrrolidone), hydroxypropyl methylcellulose, Tween 80, and sodium dodecyl sulfate as stabilizers.
[0138] After CTAB modification, the CNCs became more hydrophobic and had better compatibility with NG molecules due to the presence of the long carbon chains of CTAB. It was easier to load NG nanoparticles into the CNCs via electrostatic and hydrophobic interactions (Figure 3, c), which could further reduce the particle size and improve the stability of NG nanoparticles.
[0139] 4.2 Optimization of CNC / NG nanocomposite preparation 4.2.1 Factors and levels of orthogonal experiments Based on previous experiments, we found that for CNC / NG nanocomposites, four factors, including pH value, solvent to antisolvent volume ratio, temperature, and NG concentration, have significant effects on the hydroxyl radical (OH·) scavenging rate. In the following study, these four factors and their various levels are determined for orthogonal experiments shown in Table 2.
[0140] [Table 2]
[0141] 4.2.2 Orthogonal experiment results and analysis The L16(4^5) table was used in the orthogonal experiment, and the OH· capture rate was used as the evaluation index of the CNC / NG nanocomposite. The results and analysis of the orthogonal experiment are shown in Table 3.
[0142] [Table 3]
[0143] Based on the results and analysis of the orthogonal experiments, the combination of B3A4D3C3 was the optimal choice, and the detailed conditions for preparing CNC / NG were as follows: solvent / antisolvent volume ratio, 1:20; pH, 10; temperature, 0 °C; concentration of NG, 10 μg / ml.
[0144] However, considering that the pH value of 10 is higher than the normal pH of the human body, and according to the trend of the effect of pH on the OH· scavenging rate, pH 7.0–8.5 is used for the following preparation of CNC / NG nanocomposites.
[0145] 4.3 Characterization 4.3.1 FTIR analysis The FTIR spectra of CNC, pristine NG, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite are shown in Figure 5. -1 and 1600cm -1 The absorption peaks at 3333 cm are typical peaks of pristine NG, representing CH stretching and C=O stretching, respectively. CNC has a peak at 3333 cm -1 (OH telescopic), 1060cm -1 (secondary hydroxyl), 1030cm -1 (primary hydroxyl) peaks, which are consistent with the characteristics of cellulose.
[0146] In contrast, for the CNC / NG nanocomposite, 3333 cm -1 , 1060cm -1 , and 1030 cm -1 The absorption peak of NG increased, indicating the formation of hydrogen bonds between CNCs and NG. Moreover, the typical absorption peak of NG was observed in the CNC / NG nanocomposite.
[0147] For CNC / CTAB / NG nanocomposite, 1030 cm -1 and 1060cm -1The absorption peak of NG was further increased compared to that of CNC / NG nanocomposite, which may be attributed to the attachment of long alkyl chains from CTAB to CNC. Also, the typical absorption peak of NG was found in CNC / CTAB / NG nanocomposite, indicating that NG was successfully loaded into CNC.
[0148] Figure 5 shows the FTIR spectra of CNC, pristine NG, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite.
[0149] Figure 6 shows the XRD patterns of CNC, pristine NG, CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite.
[0150] The XRD patterns of CNC, pristine NG, CNC / NG nanocomposite, and CNC / CTAB / NG nanocomposite are shown in Fig. 6. As shown, pristine NG exhibited strong diffraction peaks at 2θ = 10.76°, 15.92°, 17.24°, 18.15°, 19.90°, 20.52°, 22.20°, 23.80°, 24.43°, 25.34°, and 27.71°, indicating that NG is in a crystalline state.
[0151] In contrast, in the CNC / NG and CNC / CTAB / NG nanocomposites, the strong diffraction peaks of NG disappeared, indicating that NG transformed from a highly crystalline state to an amorphous state. The effective nanonization of NG based on the formation of CNC / NG and CNC / CTAB / NG nanocomposites may be responsible for the transformation of the crystalline state of NG.
[0152] 4.3.3 TEM analysis It can be seen that the NG particles prepared by the traditional anti-solvent recrystallization method were needle-shaped with lengths of 0.8–1.0 μm (Figures 7a and 7b).
[0153] Figure 7 shows the TEM images of (a), (b) NG particles by traditional antisolvent recrystallization process, (c) CNC / NG nanocomposite, and (d) CNC / CTAB / NG nanocomposite.
[0154] In contrast, the NG particles were transformed into several small nanoparticles based on the formation of CNC / NG nanocomposites (Fig. 7c).CNCs, with their large surface area and abundant hydrogen bonds, could provide more sites for NG nuclei, resulting in the formation of smaller and more uniform NG nanoparticles.
[0155] Moreover, the NG particles were further dispersed and nanosized based on the formation of CNC / CTAB / NG nanocomposite (Figure 7d), which may be attributed to the increased hydrophobicity of CNC after CTAB modification. Nanoization of hydrophobic drugs can help enhance the dissolution rate and bioavailability due to the increased specific surface area.
[0156] 4.4 In vitro dissolution rate 4.4.1 Standard NG curve Various concentrations of NG in ethanol (2.4-8.4 μg / ml) were prepared and the UV absorbance at 290 nm was measured. A standard curve of NG was plotted.
[0157] The equation between NG absorbance and concentration is Y=0.00761X-0.0225, R 2 = 0.9955. The concentration and absorbance of NG showed an excellent linear relationship that could be used to determine the NG concentration.
[0158] 4.4.2 In vitro dissolution rate The dissolution rates of pristine NG, NG particles (traditional anti-solvent recrystallization process), CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite are shown in Figure 8. The dissolution rate of pristine NG was extremely limited, only 1.87% at 120 min. The dissolution rate of NG particles (traditional anti-solvent recrystallization process) increased, reaching 25.1% and 35.2% at 10 and 120 min, respectively.
[0159] In contrast, the dissolution rate of NG was obviously increased in the CNC / NG and CNC / CTAB / NG nanocomposites. For example, the dissolution rates of CNC / NG and CNC / CTAB / NG nanocomposites reached 53.6% and 78.5% at 10 min, respectively; then, the dissolution rates increased slowly and reached 92.6% and 99.5% at 120 min, respectively. The dissolution rate is well related to the bioavailability of hydrophobic drugs. In the literature, many researchers have reported that the bioavailability of hydrophobic drugs, such as quercetin and curcumin, can be effectively enhanced by increasing their dissolution rates.
[0160] Figure 8 shows the dissolution rates of pristine NG, NG particles (traditional anti-solvent recrystallization process), CNC / NG nanocomposite, and CNC / CTAB / NG nanocomposite.
[0161] 4.5 In vitro hydroxyl radical (OH ) scavenging activity The OH· scavenging activity of pristine NG, NG particles (traditional antisolvent recrystallization process), CNC, CNC / NG nanocomposite, and CNC / CTAB / NG nanocomposite are shown in Figure 9 .
[0162] It can be observed that pure CNCs exhibited excellent OH· capture efficiency, e.g., the OH· capture rate was 17.1%–21.6% at concentrations of 10–50 μg / ml, which can be attributed to the large amount of reducing end groups of CNCs.
[0163] The OH· trapping rate of pristine NG was extremely low, only 6.7% at a concentration of 50 μg / ml, which is due to the hydrophobic nature of pristine NG. In the case of NG particles (antisolvent recrystallization process), the trapping rate of OH· increased, reaching 11.2% at a concentration of 50 μg / ml.
[0164] Figure 9 shows the OH· scavenging activity of pristine NG, NG particles (traditional antisolvent recrystallization process), CNC, CNC / NG nanocomposite, and CNC / CTAB / NG nanocomposite.
[0165] In contrast, for the CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite, the OH trapping rate obviously increased to 41.2% and 52.5% at a concentration of 50 μg / ml, respectively. These results indicated that CNC and CNC / CTAB as carriers could effectively enhance the dissolution of NG. Moreover, the CNC / CTAB / NG nanocomposite showed a better OH trapping rate than the CNC / NG nanocomposite, which could be attributed to the enhanced compatibility of CTAB-modified CNC.
[0166] 5. Conclusion 5.1 CNC / NG nanocomposites and CNC / CTAB / NG nanocomposites were successfully prepared based on CNC support and antisolvent recrystallization process. TEM and XRD analyses showed that NG was effectively nanosized, well dispersed, and transformed from a highly crystalline state to an amorphous state.
[0167] 5.2 Pure CNCs have excellent hydroxyl radical (OH·) scavenging ability due to the large amount of cellulose reducing ends.
[0168] 5.3 The dissolution rates of NG in the CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite were obviously increased to 92.6% and 99.5% at 120 min, respectively, compared with that of pristine NG (1.87%). As a result, the OH· trapping rates of the CNC / NG nanocomposite and CNC / CTAB / NG nanocomposite were obviously enhanced compared with that of pristine NG.
[0169] Based on these experimental results, CNCs as carriers are promising for enhancing the bioavailability of NG due to their facile preparation method and excellent biocompatibility.
[0170] Part II: CNF as nanocarriers to enhance the dissolution and bioavailability of azithromycin
[0171] 1. Background Azithromycin (AZI, Figure 10) is a 15-membered semisynthetic macrolide antibiotic characterized by the insertion of a nitrogen atom into a 14-membered ring to form a 15-membered ring. AZI has the potent antibacterial activity of macrolides against Gram-positive and Gram-negative bacteria. Clinically, AZI is widely used to treat respiratory infections, skin and soft tissue infections, and urinary and reproductive system infections. However, similar to other water-insoluble drugs, the main challenge of AZI in pharmacology is its low oral bioavailability due to its insolubility in aqueous solutions and hydrophobic nature. Therefore, the most important thing for AZI is to enhance the drug release and bioavailability in aqueous systems.
[0172] In this study, AZI was selected as a model drug, and cellulose nanofibers (CNF) provided by UPM were used as drug carriers. CNF / AZI nanocomposites were prepared via anti-solvent recrystallization process to enhance the dissolution and bioavailability of AZI. Figure 10 shows the chemical structure of azithromycin.
[0173] 2. Research purpose 2.1 Preparation and characterization of CNF / AZI nanocomposites; 2.2 Evaluation of dissolution of AZI in CNF / AZI nanocomposite in aqueous systems
[0174] 3. Materials and Methods 3.1 Materials and Equipment Cellulose nanofibers (CNF) were obtained as 1.5% gel from UPM. Cellulose nanocrystals (CNC) were obtained as 98% lyophilized powder from Cellulose Lab Inc. (Fredericton, Canada). Azithromycin was obtained as 98% purity from Yuanzhi Biotechnology Co., Ltd. (Nanjing, China).
[0175] The main experimental equipment included an ultrasonic cell disrupter D&DN JY99-IIDN manufactured by Xinzhi Biotechnology Co., Ltd. (Zhejiang, China), a UV-vis spectrophotometer TU-1810PC manufactured by Beijing Puhua General Instrument Co., Ltd. (Beijing, China), a Fourier transform infrared spectrometer Nicolet iS5 manufactured by Thermo Fisher Company (Waltham, USA), a transmission electron microscope JEM-2010 manufactured by Electronics Corporation (Tokyo, Japan), an X-ray diffractometer Bruker D8 Advance manufactured by Bruker Company (Karlsruhe, Germany), and a freeze dryer ALPHA1-2LDPLUS manufactured by Marin Christ Co., Ltd. (Osterode, Germany).
[0176] 3.2 Experimental Method 3.2.1 Preparation of CNF / AZI nanocomposite The original AZI powder was dissolved in absolute ethanol under ultrasonic dispersion at room temperature to form a solution with a concentration of 200 μg / ml. Then, 3 ml of the AZI ethanol solution was added dropwise to the well-dispersed CNF aqueous solution (60 ml, 0.05 wt.%) with magnetic stirring in an ice-water bath, which was maintained for 10 min. Finally, the obtained CNF / AZI nanocomposite suspension was freeze-dried for future use.
[0177] For comparison, AZI particles were prepared by dropping 3 ml of AZI ethanol solution (200 μg / ml) into deionized water (60 ml) under the same conditions (traditional anti-solvent recrystallization process).
[0178] 3.2.2 Characterization (1) Fourier transform infrared spectroscopy (FTIR) analysis The CNF, pristine AZI powder, and CNF / AZI nanocomposite samples were analyzed with a Nicolet iS5 FTIR spectrometer (Thermo Fisher, Waltham, USA) at 400 cm -1 ~4000cm -1 Scans were collected within a range of
[0179] (2) Transmission electron microscope (TEM) observation Samples of CNF, pristine AZI powder, and CNF / AZI nanocomposite were diluted to 0.01 wt.% with deionized water, and one drop of the diluted dispersion was transferred onto a carbon-coated copper grid. The grid was then air-dried overnight at room temperature. TEM observations were performed using a JEM 2010 (S)TEM instrument (Japan) operating at an accelerating voltage of 200 keV.
[0180] (3) X-ray diffraction (XRD) analysis The CNF, pristine AZI powder, and CNF / AZI nanocomposite samples were analyzed on a Bruker D8 Advance powder X-ray diffractometer (Germany) operated at an accelerating voltage of 40 kV. The diffraction intensity of CuKα radiation was measured within the 2θ scan range of 3°–50° at 0.02° / s per step.
[0181] 3.2.3 In vitro hydroxyl radical (OH ) scavenging activity The in vitro antioxidant activity of the samples was evaluated by measuring the OH· scavenging activity according to the salicylic acid hydroxylation method. In this method, the Fenton reaction was used to generate OH·, which was then scavenged by salicylic acid. The system consisted of 1.8 mM ferrisulphate (2 ml), 1.8 mM salicylic acid (1.5 ml), and 1 ml of sample solution. Finally, 0.1 ml of H2O2 (0.03 wt.%) was added to the mixed solution to start the reaction, and the mixture was incubated at 37 °C for 30 min. After incubation, the UV absorption was measured at a wavelength of 510 nm. The OH· scavenging rate was calculated using Equation 1: OH Capture rate (%)=(A0-A i )×100% / A0(1) (where A0 is the UV absorbance of the control representing the total amount of OH· produced, and Ai is the UV absorbance of the sample).
[0182] 3.2.4 In vitro dissolution of AZI (1)Standard AZI curve The original AZI powder was dissolved in absolute ethanol under ultrasonic dispersion at room temperature to form a solution with a concentration of 2 mg / ml. Then, hydrochloric acid (0.1 M) was added to the AZI solution to form a series of AZI solutions with various concentrations (16 μg / ml, 32 μg / ml, 48 μg / ml, 64 μg / ml, 80 μg / ml, 96 μg / ml). Then, 5 ml of each AZI sample and 5 ml of sulfuric acid (73.5%) were added to the test tube and mixed, and then the resulting mixture was kept for reaction at room temperature for 30 minutes. Finally, the UV absorption was measured at a wavelength of 482 nm to determine the concentration of the AZI solution, and the standard AZI curve can be plotted.
[0183] (2) In vitro dissolution rate The dissolution rate was determined according to the method of the Chinese Pharmacopoeia 2015 (XC II). First, 2 mg of AZI was placed in 100 ml of deionized water and stirred at 100 rpm and 37° C. At pre-scheduled times (1 min, 5 min, 10 min, 30 min, 60 min, 120 min), 3 ml of each sample was taken out and filtered through a 0.45 μm membrane to obtain the filtrate; meanwhile, 3 ml of deionized water was immediately added to the dissolution medium to maintain a constant volume.
[0184] Then, 2 ml of sulfuric acid (73.5%) and 2 ml of the obtained filtrate were added to the test tube to form a mixture, and the mixture was maintained for 30 minutes. Finally, the UV absorption was measured at a wavelength of 482 nm to determine the AZI concentration. The dissolution rate of AZI was calculated using Equation 2: Dissolution rate (%)=(C n ×V2+C1×V1+C2×V1+…+C n-1 ×V1)×100% / m(2) (In the formula, C1, C2, C n-1 , C n is the AZI concentration at the pre-scheduled time, mg / ml; m is the total AZI input, mg; V1 is the fixed sampling volume, ml; V2 is the total volume of dissolution medium, ml).
[0185] 4. Results and Discussion 4.1 Characterization of CNFs In this study, including dispersion and stability in aqueous systems, FTIR analysis, TEM observation, and XRD analysis, CNFs from UPM R&D Center were analyzed and compared with CNCs. The results are as follows:
[0186] 4.1.1 Dispersion and stability of CNF in aqueous systems As shown in Figure 11a, CNFs are easily dispersed in deionized water at a concentration of 0.1 wt.%, but the dispersibility and stability of the CNF suspension are lower than that of the CNC suspension (Cellulose Lab Inc., Fredericton, Canada, produced by sulfuric acid hydrolysis method). In Figure 11b, CNFs become gelled and lose fluidity at a concentration of 1.5 wt.%; for comparison, CNCs still show excellent fluidity and stability at a concentration of 1.5 wt.%.
[0187] 4.1.2 TEM analysis of CNFs Figures 12a and 12b show that CNFs are typical of cellulose nanofibers, with long lengths and small diameters (5-50 nm). CNFs are more likely to form aggregates due to their long length and excellent flexibility. In contrast, CNCs are needle-like with lengths of 100-400 nm and widths of 5-40 nm (Figure 12c). Compared to CNFs, CNCs are more likely to disperse and form stable suspensions due to their short length and strong rigidity.
[0188] 4.1.3 FTIR analysis of CNFs The FTIR spectra of CNF and CNC were analyzed and compared, and are shown in Figure 13. It can be seen that CNF and CNC have similar chemical structures (cellulose structures). For example, at 3333 cm -1 , 2890cm -1 , 1060cm -1 , and 1030 cm -1 The absorption peaks were attributed to OH stretching, CH stretching, secondary hydroxyl, and primary hydroxyl, respectively. CNFs and CNCs have similar FTIR absorption because they are both prepared from high-purity raw cellulose fibers.
[0189] 4.1.4 XRD analysis of CNF The XRD patterns of CNF and CNC were analyzed and compared and shown in Figure 14. As shown, weak diffraction peaks of CNF were observed at 2θ = 15.5°, 16.5°, and 22.8°; for comparison, CNC showed strong diffraction peaks at 2θ = 12.5°, 14.7°, and 22.7°, indicating that CNC has higher crystallinity than CNF. In the case of CNC, it was explained that the amorphous regions of cellulose were removed through acid hydrolysis and the crystalline regions were preserved; however, in the case of CNF, harsh mechanical treatments including extrusion and tearing were introduced which could significantly destroy the crystalline regions of cellulose.
[0190] 4.2 Concept of preparation of CNF / AZI nanocomposite Figure 4 shows the concept of preparing CNF / AZI nanocomposite. In the traditional anti-solvent recrystallization process (upper route), the original AZI is dissolved in a solvent (absolute ethanol), and then the AZI ethanol solution is added dropwise to an anti-solvent (deionized water) under various conditions (concentration, volume ratio, temperature and stirring conditions). With increasing dosage of AZI in deionized water, AZI reaches a supersaturated state and forms a large amount of AZI nuclei. Due to the hydrophobic nature of AZI, these AZI nuclei continue to grow and eventually form AZI nanoparticles and aggregates, which are difficult to further disperse in aqueous solution.
[0191] When CNF is used as a carrier (pathway below), the large specific surface area and network structure of CNF provide more sites for AZI nucleation, prevent AZI particles from overgrowing, and make AZI nanoparticles more stable in aqueous solution. The interaction between CNF and AZI can be electrostatic adsorption and hydrogen bonding.
[0192] 4.3 Characterization of CNF / AZI nanocomposite 4.3.1 FTIR analysis The FTIR spectra of pristine AZI, CNF and CNF / AZI nanocomposite are shown in Figure 15. The results show that pristine AZI has a peak at 3486 cm, which represents OH stretching, CH stretching and C=O stretching, respectively. -1 , 2969cm -1, and 1720 cm -1 No typical absorption peaks of AZI were observed in the CNF FTIR results.
[0193] For the CNF / AZI nanocomposite, the strength was reduced, but this can be attributed to AZI, at 3486 cm -1 (OH telescopic), 2969cm -1 (CH stretch) and 1720cm -1 (C=O stretching) absorption peaks can be observed. These results indicated that AZI was successfully loaded into CNF and the chemical structure of AZI did not change.
[0194] 4.3.2 XRD analysis The XRD patterns of CNF and CNF / AZI nanocomposite are shown in Figure 16 . Pristine AZI showed strong diffraction peaks at 2θ = 8.0°, 9.8°, 16.9°, 18.9°, 20.7°, 27.3° and 42.3°, indicating that it was in a crystalline state. However, the characteristic diffraction peaks of AZI disappeared in the CNF / AZI nanocomposite, indicating that AZI transformed from a highly crystalline state to an amorphous state. The nanoization and sufficient dispersion of AZI upon the formation of CNF / AZI nanocomposite may be responsible for the transformation of AZI state. Effective nanoization of hydrophobic drugs enhances their aqueous solubility and bioavailability.
[0195] 4.3.3 TEM analysis Figure 17 shows the TEM images of pristine AZI, CNF and CNF / AZI nanocomposites. Bars are 2 μm in a) and 0.5 μm in b), c) and d). Figure 17a shows that pristine AZI was in a crystalline state and had a large particle size (several micrometers). AZI particles prepared by the traditional anti-solvent precipitation process were aggregates (Figure 17b) and were difficult to further disperse in aqueous solutions due to the hydrophobic nature of AZI.
[0196] In contrast, upon the formation of CNF / AZI nanocomposite (Figure 17d), the aggregates of AZI particles are well dispersed into several small and uniformly sized nanoparticles, which may be attributed to the electrostatic and hydrogen bonding interactions between CNF and AZI particles. AZI nanoparticles prepared by the anti-solvent recrystallization process can be easily adsorbed onto the surface of CNF; furthermore, the CNF network may help to reduce the aggregation of AZI nanoparticles.
[0197] 4.4 Hydroxyl radical (OH ) scavenging activity of CNF Our previous study showed that CNCs have excellent OH scavenging activity. Herein, the OH scavenging activity of CNFs was investigated and compared with that of CNCs, as shown in Figure 18.
[0198] It can be seen that under the same conditions, CNFs have a lower OH capture efficiency than that of CNCs. For example, the OH capture efficiency of CNFs was in the range of 5.6–6.2% at concentrations of 10–30 μg / ml; in contrast, the OH capture efficiency of CNCs was in the range of 18.4%–22.1% at the same concentrations.
[0199] It was explained that the difference in the amount of cellulose reducing ends resulted in the difference in OH capture efficiency. In the case of CNF, the longer length and smaller cross-sectional area of the fiber resulted in fewer exposed cellulose reducing ends. In contrast, in the case of CNC, the shorter length and larger cross-sectional area of the fiber resulted in a larger amount of exposed cellulose reducing ends.
[0200] 4.5 In vitro dissolution rate 4.5.1 Standard AZI curve Various concentrations of AZI in ethanol solutions (8-48 μg / ml) were prepared, and the UV absorption at 482 nm was measured to plot a standard curve of AZI. The standard curve of AZI was calculated. The equation is as follows: y=22.996x-0.0821, R 2 = 0.9991, indicating that the concentration of AZI and the absorbance have an excellent linear relationship.
[0201] 4.5.2 In vitro dissolution rate of AZI The dissolution rates of pristine AZI, AZI particles (traditional anti-solvent recrystallization process), CNC / AZI nanocomposite and CNF / AZI nanocomposite are shown in Figure 19. It can be seen that the dissolution rate of pristine AZI is very limited, only 1.31% at 120 min. Through the anti-solvent recrystallization process, the dissolution rate of AZI increases, reaching 38.8% and 52.2% at 10 min and 120 min, respectively.
[0202] In contrast, the dissolution rate of AZI was obviously increased in CNF / AZI nanocomposite and CNC / AZI nanocomposite. For example, the dissolution rate of AZI in CNF / AZI nanocomposite and CNC / AZI nanocomposite reached 80.4% and 85.1% at 10 min, respectively; then, the dissolution rate increased slowly and reached 91.2% and 96.3% at 120 min, respectively. These results indicated that CNF or CNC as carriers could effectively enhance the dissolution of AZI.
[0203] 5. Conclusion 5.1 CNF / AZI nanocomposites were successfully prepared based on CNF support and anti-solvent recrystallization process. TEM and XRD analyses showed that AZI was effectively nanosized, well dispersed, and transformed from a highly crystalline state to an amorphous state.
[0204] 5.2 The OH· capture efficiency of pure CNFs (6.2%, 30 μg / ml) was lower than that of pure CNCs (22.1%, 30 μg / ml), which was due to the lower amount of cellulose reducing ends in CNFs.
[0205] 5.3 Based on the formation of CNF / AZI nanocomposite, compared with the dissolution rate of pristine AZI (1.31%), the dissolution rate of AZI in CNF / AZI nanocomposite was obviously increased to 91.2% at 120 min.
[0206] 5.4 The prepared CNF / AZI nanocomposite is promising for enhancing the bioavailability of AZI due to its facile preparation method and excellent bioavailability.
[0207] The embodiments of the present application include the following aspects. <1> providing a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a solvent capable of at least partially solubilizing said pharmaceutical compound; Providing an aqueous dispersion of nanostructured cellulose; and combining said pharmaceutical compound with said aqueous dispersion of nanostructured cellulose in a non-solvent process to provide nano-sized pharmaceutical particles having an average diameter of 50 nm or less; A method for preparing a pharmaceutical composition comprising: <2> Item 1. The method according to item 1, wherein the pharmaceutical composition contains 92 to 99.95% (w / w) water. <3> Item 3. The method of item 1 or 2, wherein the nanostructured cellulose comprises nanofibrillar cellulose having an average fibril diameter of 200 nm or less. <4> Item 4. The method according to item 3, wherein the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 1,000 to 100,000 Pa s and a yield stress of 1 to 50 Pa, as determined by a rotational rheometer at a concentration of 0.5% (w / w) in an aqueous medium at 22°C ± 1°C. <5> Item 4. The method according to item 3, wherein the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 5,000 to 50,000 Pa s and a yield stress of 3 to 15 Pa, as determined by a rotational rheometer at a concentration of 0.5% (w / w) in an aqueous medium at 22°C ± 1°C. <6> Item 3. The method of item 1 or 2, wherein the nanostructured cellulose comprises nanocrystalline cellulose. <7> Item 7. The method according to item 6, wherein the nanocrystalline cellulose has an average fibril diameter of 2 to 40 nm and an average fibril length of 100 nm or more. <8> Item 7. The method according to item 6, wherein the nanocrystalline cellulose has an average fibril diameter of 2 to 20 nm and an average fibril length of 100 to 400 nm. <9> Item 9. The method according to any one of items 1 to 8, wherein the content of the nanostructured cellulose in the pharmaceutical composition is 0.05 to 8% (w / w). <10> Item 10. The method according to item 9, wherein the content of the nanostructured cellulose in the pharmaceutical composition is 0.05 to 0.5% (w / w) or 1 to 8% (w / w). <11> Item 11. The method according to any one of items 1 to 10, wherein the pharmaceutical compound has a solubility in water of 0.6 mg / ml or less at 25° C. and / or low bioavailability. <12> Item 12. The method according to any one of items 1 to 11, wherein the pharmaceutical compound has a solubility in water of 0.3 mg / ml or less at 25° C. and / or low bioavailability. <13> Item 13. The method according to any one of items 1 to 12, wherein the pharmaceutical compound has a solubility in water of 0.1 mg / ml or less at 25° C. and / or low bioavailability. <14> Item 14. The method according to any one of Items 1 to 13, wherein the content of the pharmaceutical compound is 0.05 to 1 mg per 100 μl of the pharmaceutical composition. <15> Item 15. The method according to any one of Items 1 to 14, wherein the content of the pharmaceutical compound is 0.1 to 0.7 mg per 100 μl of the pharmaceutical composition. <16> Item 16. The method according to any one of Items 1 to 15, wherein the content of the pharmaceutical compound is 0.1 to 0.5 mg per 100 μl of the pharmaceutical composition. <17> A method for stabilizing a pharmaceutical compound having a low solubility in water of 1 mg / ml or less, comprising preparing a pharmaceutical composition by the method according to any one of items 1 to 16. <18> A pharmaceutical composition comprising nano-sized pharmaceutical particles of a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a nanostructured cellulose matrix, said nano-sized pharmaceutical particles having a mean diameter of 50 nm or less. <19> Item 19. The pharmaceutical composition according to item 18, comprising 92 to 99.95% (w / w) water. <20> Item 20. The pharmaceutical composition according to item 18 or 19, wherein the nanostructured cellulose comprises nanofibrillar cellulose having an average fibril diameter of 200 nm or less. <21> Item 21. The pharmaceutical composition according to any one of Items 18 to 20, wherein the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 1,000 to 100,000 Pa s and a yield stress (shear stress at which shear thinning begins) of 1 to 50 Pa, as determined by a rotational rheometer at a concentration of 0.5% (w / w) in an aqueous medium at 22°C ± 1°C. <22> Item 22. The pharmaceutical composition according to any one of Items 18 to 21, wherein the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 5,000 to 50,000 Pa s and a yield stress (shear stress at which shear thinning begins) of 3 to 15 Pa, as determined by a rotational rheometer at a concentration of 0.5% (w / w) in an aqueous medium at 22°C±1°C. <23> 20. The pharmaceutical composition of claim 18 or 19, wherein the nanostructured cellulose comprises nanocrystalline cellulose. <24> Item 24. The pharmaceutical composition according to Item 23, wherein the nanocrystalline cellulose has an average fibril diameter of 2 to 40 nm and an average fibril length of 100 nm or more. <25> Item 24. The pharmaceutical composition according to Item 23, wherein the nanocrystalline cellulose has an average fibril diameter of 2 to 20 nm and an average fibril length of 100 to 400 nm. <26> Item 26. The pharmaceutical composition according to any one of Items 18 to 25, wherein the content of the nanostructured cellulose in the pharmaceutical composition is 0.05 to 8% (w / w). <27> Item 27. The pharmaceutical composition according to item 26, wherein the content of the nanostructured cellulose in the pharmaceutical composition is 0.05 to 0.5% (w / w) or 1 to 8% (w / w). <28> Item 28. The pharmaceutical composition according to any one of Items 18 to 27, wherein the pharmaceutical compound has a solubility in water of 0.6 mg / ml or less at 25° C. and / or low bioavailability. <29> Item 29. The pharmaceutical composition according to any one of Items 18 to 28, wherein the pharmaceutical compound has a solubility in water of 0.3 mg / ml or less at 25° C. and / or low bioavailability. <30> Item 30. The pharmaceutical composition according to any one of Items 18 to 29, wherein the pharmaceutical compound has a solubility in water of 0.1 mg / ml or less at 25° C. and / or low bioavailability. <31> Item 31. The pharmaceutical composition according to any one of Items 18 to 30, wherein the content of the pharmaceutical compound is 0.05 to 1 mg per 100 μl of the pharmaceutical composition. <32> Item 32. The pharmaceutical composition according to any one of Items 18 to 31, wherein the content of the pharmaceutical compound is 0.1 to 0.7 mg per 100 μl of the pharmaceutical composition. <33> Item 33. The pharmaceutical composition according to any one of Items 18 to 32, wherein the content of the pharmaceutical compound is 0.1 to 0.5 mg per 100 μl of the pharmaceutical composition. <34> Item 34. The pharmaceutical composition according to any one of items 18 to 33, wherein the dissolution rate of the pharmaceutical compound from the nanostructured cellulose matrix is 50% or more in 10 minutes. <35> Item 35. The pharmaceutical composition according to any one of items 18 to 34, wherein the dissolution rate of the pharmaceutical compound from the nanostructured cellulose matrix is 50 to 90% in 10 minutes. <36> The pharmaceutical composition according to any one of items 18 to 35, obtained by the method according to any one of items 1 to 17. <37> Item 37. The pharmaceutical composition according to any one of items 18 to 36, which is filled in a vial, a capsule or a syringe. <38> Item 38. The pharmaceutical composition according to any one of Items 18 to 37, for use as a medicament for enhancing the bioavailability of a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. <39> Item 18. Use of nanostructured cellulose for stabilizing a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. by the method according to any one of items 1 to 17.
Claims
1. A method for preparing a pharmaceutical composition, comprising: providing a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a solvent, the solvent comprising an organic solvent, capable of at least partially solubilizing said pharmaceutical compound; Providing an aqueous dispersion of nanostructured cellulose; and an anti-solvent recrystallization process, adding said pharmaceutical compound in said solvent to said aqueous dispersion of nanostructured cellulose acting as an anti-solvent to obtain a supersaturated concentration of said pharmaceutical compound, said pharmaceutical compound nucleating at said supersaturated concentration and then continuing to grow by nucleation into nanoparticles, thereby providing nano-sized pharmaceutical particles having an average diameter of 50 nm or less; Including, The method, wherein the pharmaceutical composition comprises 92-99.95% (w / w) water.
2. 2. The method of claim 1, wherein the nanostructured cellulose comprises nanofibrillar cellulose having an average fibril diameter of 200 nm or less.
3. 3. The method of claim 2, wherein the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 5000-50000 Pa s and a yield stress of 3-15 Pa, as determined by a rotational rheometer at a concentration of 0.5% (w / w) in an aqueous medium at 22°C±1°C.
4. 2. The method of claim 1, wherein the nanostructured cellulose comprises nanocrystalline cellulose.
5. 5. The method of claim 4, wherein the nanocrystalline cellulose has an average fibril diameter of 2 to 20 nm and an average fibril length of 100 to 400 nm.
6. The method according to any one of claims 1 to 5, wherein the content of said nanostructured cellulose in said pharmaceutical composition is 0.05 to 8% (w / w).
7. 7. The method of claim 6, wherein the content of said nanostructured cellulose in said pharmaceutical composition is 0.05-0.5% (w / w), or 1-8% (w / w).
8. The method according to any one of claims 1 to 7, wherein the pharmaceutical compound has a solubility in water of less than 0.6 mg / ml at 25°C and / or a low bioavailability.
9. The method according to any one of claims 1 to 8, wherein the content of the pharmaceutical compound is 0.05 to 1 mg per 100 µl of the pharmaceutical composition.
10. The method of claim 1, wherein the solvent comprises ethanol.
11. The method according to any one of claims 1 to 10, comprising freeze-drying the obtained pharmaceutical composition.
12. A method for stabilizing a pharmaceutical compound having a low solubility in water of 1 mg / ml or less, comprising preparing a pharmaceutical composition according to the method of any one of claims 1 to 11.
13. nano-sized pharmaceutical particles of a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in a nanostructured cellulose matrix, said nano-sized pharmaceutical particles having a mean diameter of 50 nm or less; Contains 92-99.95% (w / w) water; A pharmaceutical composition obtainable by the method according to any one of claims 1 to 11.
14. 14. The pharmaceutical composition of claim 13, wherein the nanostructured cellulose comprises nanofibrillar cellulose having an average fibril diameter of 200 nm or less.
15. 15. The pharmaceutical composition of claim 14, wherein the nanofibrillar cellulose, when dispersed in water, has a zero shear viscosity of 5,000-50,000 Pa s and a yield stress (shear stress at which shear thinning begins) of 3-15 Pa, as determined by a rotational rheometer at a concentration of 0.5% (w / w) in an aqueous medium at 22°C±1°C.
16. 14. The pharmaceutical composition of claim 13, wherein the nanostructured cellulose comprises nanocrystalline cellulose.
17. 17. The pharmaceutical composition of claim 16, wherein the nanocrystalline cellulose has an average fibril diameter of 2 to 20 nm and an average fibril length of 100 to 400 nm.
18. The pharmaceutical composition according to any one of claims 13 to 17, wherein the content of said nanostructured cellulose in said pharmaceutical composition is 0.05 to 8% (w / w).
19. 19. The pharmaceutical composition of claim 18, wherein the content of said nanostructured cellulose in said pharmaceutical composition is 0.05-0.5% (w / w), or 1-8% (w / w).
20. The pharmaceutical composition according to any one of claims 13 to 19, wherein the pharmaceutical compound has a solubility in water of less than 0.6 mg / ml at 25°C and / or low bioavailability.
21. The pharmaceutical composition according to any one of claims 13 to 20, wherein the content of the pharmaceutical compound is 0.05 to 1 mg per 100 μl of the pharmaceutical composition.
22. A pharmaceutical composition according to any one of claims 13 to 21, wherein the dissolution rate of the pharmaceutical compound from the nanostructured cellulose matrix is greater than or equal to 50% in 10 minutes.
23. A pharmaceutical composition according to any one of claims 13 to 22 for use as a medicament for enhancing the bioavailability of a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25°C.
24. Use of nanostructured cellulose for stabilizing a pharmaceutical compound having a solubility in water of 1 mg / ml or less at 25° C. in the method according to any one of claims 1 to 11.
Citation Information
Patent Citations
Drug delivery systems for sustained delivery of bioactive agents
JP2014533296A
Paramylon aqueous dispersion and cell proliferation promoter
JP2017155195A
Supersaturated stabilized nanoparticles for poorly soluble drugs
US20150335753A1